Eucalyptus globulus and Cymbopogon flexuosus essential oils antimicrobial and conservative effects against Salmonella enterica serovar typhimurium and possible cytotoxicity: an in vitro and in situ investigation in inoculated pork sirloin - Cleiton Jesus Andrade Pereira; Vithor Parada Garcia; Vitória Rose de Andrade; Milena Mattes Cerveira; Jéssica Silveira Vitoria; David de Andrade Cabral; Eliezer Avila Gandra; Janice Luehring Giongo; Rodrigo de Almeida Vaucher (Brazilian Journal of Microbiology, 2026)
Foodborne illnesses, particularly those caused by Salmonella spp., represent a major global health concern, with S. typhimurium being a significant contributor to outbreaks. The persistence of S. typhimurium in food production environments and its resistance to conventional disinfectants highlight the need for alternative antimicrobial solutions. Essential oils (EOs) from Eucalyptus globulus (EGEO) and Cymbopogon flexuosus (CFEO) have shown antimicrobial potential against S. typhimurium , but their mechanisms of action and cytotoxic effects on eukaryotic cells require further investigation to assess their safety for food applications, particularly in situ. We evaluated cytotoxicity in erythrocytes and zebrafish liver (ZF-L) cells using hemolysis (HA), MTT, and NR uptake assays. Additionally, we investigated the antimicrobial behavior of EGEO and CFEO against S. typhimurium ATCC 14,028 through MIC/MBC tests, time-kill assays, and a newly designed TSI-adapted test to assess the EOs’ impact on bacterial metabolism. An in situ experiment was also conducted to evaluate the preservative effects of EGEO and CFEO on pork sirloin contaminated with an infectious dose of S. typhimurium and treated with EO-based brines for 7 days under refrigeration. We monitored the presence of Salmonella spp., as well as pH, calcium (Ca²⁺), and magnesium (Mg²⁺) concentrations in the brined samples. Results indicated that CFEO was hemolytic above 0.73 mg/mL and EGEO above 0.45 mg/mL. The MTT assay showed that CFEO did not impair mitochondrial function from 2.941 mg/mL and EGEO from 14.36 mg/mL. NR uptake assay showed that both EOs did not impaired lysossomal function in ZF-L. The MICs and MBCs for CFEO and EGEO were 0.37 mg/mL and 1.79 mg/mL, respectively. Time-kill assays revealed bactericidal effects for CFEO at 4x and 2x MIC within 6 h, while EGEO showed a bactericidal effect only at 4x MIC. The EO-TSI agar assay demonstrated that EGEO inhibited sugar fermentation and sulfur metabolism, while CFEO impacted peptone oxidation and protein metabolism. In situ analyses showed CFEO caused more significant changes in color and odor of the pork samples than EGEO, while both maintained pH levels around 6. Ca²⁺ and Mg²⁺ levels were lower in CFEO-treated samples. Microbiological data confirmed the absence of Salmonella spp. in all samples except for two in the CFEO-brine group. None of the samples showed signs of autolysis or putrefaction, suggesting that both CFEO and EGEO, particularly EGEO, are feasible alternatives as food preservatives, depending on the desired application.

Jaguar Range‐Wide Connectivity: Prioritising Core Areas and Corridors Between and Within Protected Areas and Indigenous Lands - Guilherme Costa Alvarenga; Caroline C. Sartor; Ana Carolina Srbek‐Araujo; Ana Cristina Mendes‐Oliveira; Bart Harmsen; Carlos De Angelo; Carolina Franco Esteves; Claudia Bueno de Campos; Daiana Jeronimo Polli; Diego F. Passos Viana; Diogo Maia Gräbin; Emiliano Donadio; et al. (Global Change Biology, 2026)
Anthropogenic habitat transformation has led to population declines and increasing isolation of populations of many species, particularly top predators, where small and fragmented populations often experience limited dispersal and reduced genetic diversity. Jaguars ( Panthera onca ), for example, have lost half of their historical range and most populations outside the Amazon biome are small, isolated and highly threatened. Here, we assess jaguar population connectivity across the species' range by identifying and ranking core areas and dispersal corridors, including linkages among Protected Areas and Indigenous Lands (hereafter, PAs). We used cumulative resistant kernels and factorial Least‐Cost Paths (fLCP) in two complementary approaches: core area‐based and PA‐based connectivity. We identified 307 core areas for jaguar movement, covering ~7.75 million km 2 (55% of the current range), of which approximately half lies within PAs. The largest and highest‐ranked core area spans ~6.5 million km 2 across four biomes (Amazon, Llanos, Chaco and Pantanal). We identified 176 dispersal corridors connecting core areas, although connectivity was not continuous across the entire range. Northern populations (Mexico and Central America) showed several connectivity gaps, whereas South America displayed a large, highly interconnected network linking the Amazon, Llanos, Chaco, Pantanal, Cerrado, Caatinga, Iberá and the Atlantic Forest's Green Corridor. In contrast, coastal Atlantic Forest patches appeared largely isolated. The PA‐based analysis predicted 507 potential corridors connecting 905 PAs, including potential links absent from the core area model, particularly across Central America and between the Darién Gap, Amazon and coastal Atlantic Forest. The core‐area approach provides a more biologically realistic representation of current connectivity, while the PA‐based approach complements it by identifying pragmatic opportunities for long‐term connectivity conservation. Together, these approaches identify priority areas and regions of uncertainty, providing a spatial framework to guide jaguar conservation and connectivity planning under accelerating global change.

Circulating metabolomic and chemical exposomics signatures as potential biomarkers for long-term radon exposure - Vrinda Kalia; Aravind Lathika Rajendrakumar; Rodrigo Cruz-Nieto; Andrea Ramírez; Jonathan González-Ruíz; Renu Nandakumar; Hanisha Udhani; Brooklynn McNeil; Changchun Xie; Saurabh Dubey; Claudia Garcia-Cuellar; David Cantú-de-León; et al. (Environmental Research, 2026)

Effects of including fodder beet or swedes in a grass, silage and concentrate-based diet on performance, rumen metabolism and N excretion of lactating dairy cows - Juan P. Keim; Víctor Leighton; Mónica Gandarillas; Rodrigo Arias; I. Beltrán; David Pacheco (Animal Feed Science and Technology, 2026)

Lycopene in citrus fruit: biochemical mechanisms, molecular insights and health implications - Jaime Zacarías-García; David Karp; Jon Roberts; Carlos Tornero-Raga; Lorenzo Zacarías; María Jesús Rodrigo (Critical Reviews in Food Science and Nutrition, 2026)

New extensions of Cell2Fire software for fire risk analysis and evaluation in Chilean forests - Jaime Carrasco-Barra; José Ramón González-Olabarria; Camilo Matus-Olivares; Felipe Ulloa-Fierro; Felipe Soto; David Palacios; Rodrigo Mahaluf; Felipe de la Barra; Carolina Espinoza; Matías Vilches; Matilde Rivas; Fernando Badilla; et al. (Environmental Modelling & Software, 2026)

Daily evolution of the indoor air concentrations of bacteria and fungi in primary school classrooms of Madrid - Luis Alou; Kevin Sabariego-Moreno; Ma Dolores Redondas Marrero; Jose Ramón Aira-Zunzunegui; Begoña Pérez-Moneo; María Aparicio Rodrigo; María del Mar Barbero-Barrera; David Sevillano (Atmospheric Pollution Research, 2026)

Flux Science Without Borders: Strengthening Ecosystem Flux Capacity in Latin America - Tonantzin Tarin; M. Susana Alvarado‐Barrientos; Eugenia González del Castillo; Mónica Cervantes‐Jiménez; Zulia Sánchez‐Mejía; Alejandro Cueva; Alejandro Delgado‐Guerrero; Dulce Flores‐Renteria; Jaime Garatuza‐Payan; César Hinojo‐Hinojo; Karem Meza; David J. P. Moore; et al. (Global Change Biology, 2026)
The future of how we understand and manage ecosystems largely depends on direct and continuous observations that connect local territories to planetary processes. Latin America (LATAM: Mexico, Central and South America, and the Caribbean) hosts ecosystems critical for regulating global carbon, water, and energy cycles. However, persistent underinvestment in science and technology hampers the long‐term monitoring capacity needed to advance regional priorities. Addressing the climate crisis requires investing in local researchers, technicians, and students, providing Earth System Science training that integrates biophysical and sociocultural knowledge. Although English is the lingua franca of science, training in native languages accelerates technical capacity, strengthens regional collaboration, and grounds solutions in local experience. Here, we present TAFE ( Taller de Aprendizaje de Flujos Ecosistémicos ) as an example of how regionally grounded, native‐languages training can strengthen ecosystem flux science in LATAM and beyond. Such initiatives help decentralize knowledge, reduce the underrepresentation of Global South ecosystems in flux databases, and empower the next generation to lead research for both regional and global benefit.

First confirmation of Caribbean ciguatoxins in fish samples from the South Atlantic coast of Brazil - Rodrigo Hoff; David Castro; Jorge Giráldez; Jose Manuel Leão-Martins; Ana Gago-Martínez (Food Research International, 2026)

Rainy and dry conditions in the state of Santa Catarina, southern Brazil: Natural variability and the ongoing warming climate - Paulo Rodrigo Zanin; David Pareja-Quispe; Renato Pattaro Pereira (Theoretical and Applied Climatology, 2026)

Long‐Term Variability in Southward Atmospheric Flows Over South America: Improving the Current Understanding - Paulo Rodrigo Zanin; David Pareja‐Quispe (International Journal of Climatology, 2026)
The southward atmospheric flows over the Chaco region in South America are important in transporting heat and moisture from the tropics to the subtropics. The intensity and frequency of these flows are modulated by climatic variability at different time scales. However, previous studies show discrepancies in the relationships between these flows and the multidecadal variabilities, such as the Atlantic Multidecadal Oscillation (AMO) and the Pacific Decadal Oscillation (PDO). Therefore, this study utilised a longer time series from the more recent and detailed reanalysis, considering the entire time series and all seasons, without and with criteria/indices for the South American Low‐Level Jet (SALLJ), in addition to further statistical analyses and a new approach to assessing the impacts of the combined phases of the AMO and the PDO, to understand in greater detail these atmospheric relationships over the Chaco region. In synthesis, the present study found that, in an isolated form, the PDO has a stronger influence than the AMO on southward atmospheric flows over the Chaco region in South America. The PDO predominantly shows a positive relationship with these atmospheric flows (mainly in the winter and spring seasons), while the AMO shows an inverse relationship with the southward atmospheric flows over the Chaco region during the South American Monsoon. In a combined form, the association of positive phases of both the AMO and the PDO (neutral AMO and negative PDO) provides the most favourable (unfavourable) conditions for southward atmospheric flows from the tropics to the subtropics in South America.

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

A framework for updating the regulation of isolated power systems in light of the energy transition imperative: The case of Chile - Cristiane Silva-Carvalho; Johanna Höhl; Carlos Olivos; Juan Carlos Osorio-Aravena; Rodrigo Palma-Behnke; Dasla Pando-Flores; Bernardo Severino; David Watts; Daniel Olivares; Alejandro Angulo; Joaquín Lazo; Humberto Vidal (Utilities Policy, 2026)

A chromosome-scale reference genome and integrative transcriptome provide insight into tissue- and stress-specific responses in tetraploid sainfoin (Onobrychis viciifolia) - Cuong V. Nguyen; Dustin Cram; Halim Song; Rodrigo Ortega Polo; Hari Poudel; Bill Biligetu; Kimberley Burton Hughes; Surya Acharya; David Konkin; Stacy D. Singer (Planta, 2026)
Main conclusion A haplotype-resolved, chromosome-scale AAC Mountainview sainfoin genome sequence along with organelle assemblies, methylome, and comparative tissue/stress-specific transcriptomes provide a solid foundation to support downstream sainfoin breeding efforts. Abstract Sainfoin ( Onobrychis viciifolia Scop.) is an outcrossing, perennial forage crop valued for its leguminous nature, nutritional quality, palatability, and production of condensed tannins, which reduce the incidence of pasture bloat in ruminants and improve feed efficiency. However, despite its potential, there remains a paucity of research and breeding efforts focusing on this species. In this study, we report the generation of a haplotype-resolved, chromosome-scale reference genome sequence for a genotype of the tetraploid sainfoin cultivar AAC Mountainview, which was assembled using PacBio HiFi, Oxford Nanopore, Illumina short read, and Hi-C data. The 2.36 Gb assembly resolves all 28 pseudochromosomes, corresponding to 4 haplotypes of the 7 base chromosomes, with high contiguity and gene completeness, as well as reference-grade long terminal repeat (LTR) assembly index (LAI) scores across all haplotypes. Nanopore-based methylation profiling revealed typical gene body CG methylation, as well as high levels of transposable element methylation. We annotated 117,890 high-confidence protein-coding genes and identified large tandem arrays of rDNA localized on unanchored but chromosome-associated scaffolds. Mitochondrial and chloroplast genomes were also successfully assembled for this genotype. Furthermore, tissue- and stress-specific transcriptomic profiling revealed both shared and distinct gene expression responses across tissue and stress types. Allele-specific expression analysis showed largely balanced haplotype activity, with subtle but consistent shifts in allelic dominance under stress. The data provided in this study offer a valuable resource for downstream breeding endeavors in this promising forage crop.

Empathy in Adults with Acquired Brain Injury: a Systematic Review and Meta-Analysis - Emily Clements; Kristin Naragon-Gainey; Michael Weinborn; Carmela Pestell; Dawn Neumann; David Preece; Rodrigo Becerra (Neuropsychology Review, 2026)
Empathy is the ability to recognise, share and understand others’ emotional states. Increasing evidence suggests that empathy may be impacted by acquired brain injury (ABI), with consequences for social and emotional functioning. However, the literature has been characterised by inconsistent findings and small sample sizes. To address these limitations, we provide the first meta-analytic review of empathy in adults with ABI. Specifically, the review aimed to quantify the degree of impairment in adults with ABI across four empathy-related domains: cognitive, affective, empathic concern (e.g. sympathy) and personal distress. We also sought to estimate the prevalence of deficits in each area and explore whether demographic and injury factors moderate impairment. A systematic search yielded 29 studies measuring self-reported empathy in adults with ABI versus healthy, matched peers. A series of random-effects meta-analyses revealed moderate deficits in cognitive empathy (Hedges’ g = − 0.68, 95% CI [− 0.87, − 0.50]) and affective empathy (Hedges’ g = − 0.43, 95% CI [− 0.65, − 0.21]), as well as small-to-moderate deficits in empathic concern (Hedges’ g = − 0.38, 95% CI [− 0.63, − 0.13]). No significant difference was found for personal distress. We estimated the proportion of ABI participants scoring equal to or more than 1 SD below the normative mean to be 15.3–35.0%, depending on the empathy subcomponent. Our results highlight that empathy deficits may play an important role in functional or emotional difficulties post-brain injury. This demonstrates the need for routine clinical assessment of empathy in survivors of brain injury and the need to develop interventions which target both cognitive and affective components.

Psilocybin-induced neurocardiogenic syncope: a case report - Mazen A. Atiq; Eli Weisman; Rodrigo B. Guerra; Luis Luna Martinez; David B. Yaden; Frederick S. Barrett; Sandeep Nayak; Ceyda Sayali (Psychopharmacology, 2026)
Background Psilocybin is among the serotonergic psychedelics closest to potential FDA approval, with growing evidence of therapeutic benefit across psychiatric conditions. As clinical trials expand, systematic characterization of adverse events (AEs) remains essential. While transient hypertensive responses are well documented, hypotensive events such as neurocardiogenic syncope (NCS) are rarely reported. Case presentation We describe a healthy 35‑year‑old male enrolled in an open‑label study investigating psilocybin‑evoked changes in brain function during transcranial magnetic stimulation and electroencephalography (TMS‑EEG). Approximately 60 minutes after receiving 25 mg oral psilocybin, and shortly after initiation of an eye‑open resting‑state EEG, he experienced prodromal lightheadedness followed by a brief loss of consciousness and postural tone. Immediate blood pressure was 93/51 mmHg with tachycardia and diaphoresis. Supportive measures, including leg elevation and oral hydration, led to rapid stabilization, and no further cardiovascular abnormalities occurred. The participant reported an emotionally intense experience, and contextual factors - including upright seated posture, restrictive EEG equipment, and anticipatory anxiety surrounding TMS - may have contributed to heightened autonomic arousal and susceptibility to NCS. Conclusions This case highlights a rare hypotensive AE during psilocybin administration and underscores the importance of vigilant cardiovascular monitoring, particularly during procedures that may amplify emotional arousal. Given that fewer than one‑quarter of contemporary psychedelic trials report systematic AE assessment, transparent documentation of both hypertensive and hypotensive events is critical for defining psilocybin’s safety profile as clinical applications expand. Parent trial registration Open Label Psilocybin Brain Stimulation and Imaging Pilot Study; ClinicalTrials.gov: NCT06835699. Date registered: 02/13/2025. The parent‑study consent form explicitly permits publication of de‑identified participant data, and separate institutional approval for this case report was obtained (IRB00543773).

Natural Dietary Supplementation with Elionurus muticus Essential Oil Enhances Growth Performance and Modulates Physiological Responses to Transport Stress in Nile Tilapia - Aline da Silva Rocha; José Fernando Bibiano Melo; David Ramos da Rocha; Rafael Carvalho da Silva; Rafael Silva Marchão; Alane Pains Oliveira do Monte; Gabriela Cristina da Silva Santos; Samantha Chung; Leandro Licursi de Oliveira; Denise Schmidt; Rodrigo Fortes-Silva; Carlos Eduardo Copatti (Fishes, 2026)
This study evaluated the effects of dietary Elionurus muticus essential oil (EMEO) on growth performance, physiological responses, and resistance to car transport stress in Nile tilapia (Oreochromis niloticus). Fish were fed experimental diets for 60 days and subsequently subjected to 6 h of transport stress. Five diets were tested: 0.00 (control), 0.25, 0.50, 1.00, and 1.50 mL EMEO kg−1, in triplicate (10 fish per 500 L tank; stocking density 0.4 kg L−1). Citral was the major EMEO compound (73.91%). Increasing dietary EMEO levels improved growth performance and reduced the feed conversion ratio. Before transport, EMEO supplementation increased erythrocyte counts and plasma glucose levels, while reducing hematocrit and hepatic aspartate aminotransferase (AST) activity (p

Dose-dependent cerebral metabolic impairment in a swine model of carbon monoxide poisoning - Alistair Lewis; Rodrigo M. Forti; Tiffany S. Ko; John C. Greenwood; Matthew Kelly; Frances S. Shofer; Shih-Han Kao; Samuel S. Shin; Devesh Bungatavula; Mckenna Mason; Jonathan Starr; Johannes K. Ehinger; et al. (NeuroToxicology, 2026)

Archean tectonics resembled modern-style plate tectonics? Pre-Columbia early plate tectonics in the São Francisco-Congo Craton - Rodrigo I. Cerri; Richard M. Palin; David Chew; Nick M.W. Roberts; Fabrício A. Caxito; Renato Moraes; George L. Luvizotto; Silvia Volante; Christopher Spencer; Claudio Riccomini (Earth and Planetary Science Letters, 2026)

Mapping Escolar ( Lepidocybium flavobrunneum ) in Motion: Oceanographic Forces Shaping Its Habitat in the Southwestern South Atlantic, With Insights From Fishers' Perceptions - Lucas Rodrigues; Maria Grazia Pennino; Paul Gerhard Kinas; David Conesa; Alba Fuster‐Alonso; Andrés Domingo; Rodrigo Forselledo; Federico Mas; Bruno Mourato; Rodrigo Sant'Ana; Vinni Santos Thykjaer; Raquel Virginia Marquez Marquez; et al. (Fisheries Oceanography, 2026)
Lepidocybium flavobrunneum [Smith, 1843], commonly known as escolar, is a large pelagic species, important for global and local fisheries, particularly in the southwestern South Atlantic Ocean (SWAO), where it constitutes a significant portion of the catch. However, despite its important socioeconomic role, it remains less studied compared to other large pelagic species. Enhancing research efforts is therefore key to better understanding the ecological processes that influence its spatial and temporal distribution. To address this gap, our study applied species distribution models (SDMs) to escolar's occurrence and abundance using longline fleet data from south Brazil and Uruguay. Estimation and prediction were conducted at the Bayesian framework using the integrated nested Laplace approximation (INLA) methodology combined with the stochastic partial differential equation (SPDE) approach. Our findings reveal a strong correlation between warmer sea surface temperatures and increased escolar occurrence and abundance in the SWAO, particularly during the austral summer, in contrast to cooler‐season patterns observed elsewhere. Escolar's distribution is influenced by the southward and westward movement of seawater driven by the Brazil Current, and its preference for depths greater than 2000 m reflects its oceanic nature. Predicted areas of higher abundance around the continental slope (between 33° and 37° S) and the Rio Grande Rise are linked to the dynamic interaction of warm and cold currents and nutrient‐rich waters. Additionally, escolar's sensitivity to low‐light conditions may explain reduced catches during moonlit nights. A complementary analysis assessing the synergistic influence of sea surface temperature and lunar illumination on escolar occurrence indicated that, under high temperatures (> 22 °C), occurrence is further enhanced during dark nights. Furthermore, semi‐structured interviews with vessel captains revealed that 90% identified temperature (via open‐ended responses) as a key environmental factor driving escolar catches, and 80% of them attributed a strong influence (greater than average catch rates) to temperature, summer season and new moon phase. This study provides new insights into escolar's seasonal and spatial patterns, emphasizing the impact of oceanographic features and light conditions on its distribution. It also highlights the need for further research into the mechanisms driving escolar populations.

The threat of multidrug-resistant microorganisms: active surveillance of key antimicrobial resistant pathogens in 2025 - a report from the INVIFAR network - Adrián Martínez-Meléndez; Elvira Garza-González; María del Rosario Vázquez-Larios; Melissa Garibaldi-Rojas; Bernardo Alfonso Martinez-Guerra; Christian Daniel Mireles-Davalos; Samuel Pavel Escalante-Armenta; José Manuel Feliciano-Guzmán; Daniel Romero-Romero; Maria del Consuelo Velazquez-Acosta; Sandra Quintana-Ponce; Shaúl Ariel Navarro-Lara; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)
Purpose Systematic collection and analysis of antimicrobial resistance data from key bacterial pathogens is essential to contribute to control antimicrobial resistance (AMR). The aim of this work was to survey the drug resistance on clinically relevant organisms stratified according to age, gender, clinical specimens and facilities. Methods Microbiological data were collected from 55 centers across 24 states in Mexico between January 1 and March 31, 2025. Bacterial identification and antimicrobial susceptibility testing were performed at each participating center using locally available methods. Data was processed using WHONET 2025. Isolates obtained from lower respiratory specimens, urine, blood, biopsies and abscesses were analyzed. Carbapenem non-susceptible isolates were further analyzed by PCR for common carbapenemase-encoding genes. Resistance frequencies were compared using the chi-square test. Results A total of 11,290 clinical isolates were analyzed, mostly from urine ( n = 7,149; 63.3%), followed by blood ( n = 1,370; 12.1%). The most prevalent was Escherichia coli ( n = 6,185; 54.8%), followed by Klebsiella pneumoniae ( n = 1,365; 12.1%) and Pseudomonas aeruginosa ( n = 1,110; 9.8%). Resistance to carbapenems in E. coli was higher in respiratory isolates (imipenem: 5.8%, p = 0.016; meropenem: 5.3%, p < 0.001), with 75.9% producing extended-spectrum ß-lactamases (ESBLs). K. pneumoniae had the highest resistance to ampicillin/sulbactam (52.5%, p = 0.028) and sulfamethoxazole/trimethoprim (62.1%, p = 0.014) in blood isolates, and 63.2% were ESBL-producers ( p = 0.001). In P. aeruginosa , urine isolates showed significantly higher resistance to ceftolozane-tazobactam (24.7%, p = 0.008), ceftazidime-avibactam (36.6%, p < 0.001), and meropenem (34.5%, p = 0.009) compared to other clinical specimens included. For A. baumannii , respiratory isolates had 73.6% resistance to meropenem ( p < 0.001). S. aureus from blood showed 25.7% resistance to oxacillin ( p < 0.004). The most frequent carbapenemase genes were bla OXA−48−like in E. coli (26/56, 46.4%), bla NDM for K. pneumoniae (7/17, 41.2%), bla OXA−24 in A. baumannii (79/108, 73.1%) and bla IMP for P. aeruginosa (18/108, 16.7%). Conclusion This surveillance study underscores the elevated levels of antimicrobial resistance, ESBL production, and carbapenemase activity among priority pathogens, including some Enterobacterales , P. aeruginosa , and A. baumannii . These findings emphasize the urgent need to strengthen epidemiologic surveillance programs in Mexican healthcare settings.

Circular and Sustainable Business Model Innovation: Formulating an Integrated Concept Through A Systematic Literature Review - Andreza Rodrigues de Araujo; Rodrigo Marques de Almeida Guerra; David Lorenzi Junior; Jordana Marques Kneipp; Luísa Margarida Cagica Carvalho (Circular Economy and Sustainability, 2026)
Despite the significant growth in research on the triad of Circular Economy (CE), Innovation, and Sustainable Business Models (SBMs), theoretical fragmentation persists due to the lack of holistic conceptual integration, resulting in a heterogeneous framework that is difficult to apply in practice. Given this scenario, this study aimed to identify, categorize, and systematize the state of the art of Circular Economy, Innovation, and Sustainable Business Models, aiming to increase conceptual clarity and strengthen the application of these concepts in theory and practice. At the same time, we sought to map emerging trends, opportunities, challenges, and future directions capable of supporting the work of academics, practitioners, and public policymakers. To this end, we conducted a systematic literature review based on the Scientific Procedures and Rationales for Systematic Literature Reviews (SPAR-4-SLR) and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols, resulting in the final selection of 60 publications extracted from the Scopus database. The results suggest that research in this field is emerging, rapidly expanding, and with increasing diversity of applications across different contexts and sectors, although still concentrated in developed countries and at an early stage of scientific maturity, marked by the predominance of systematic reviews and case studies. A thematic evolution was also observed, moving from a focus on climate change and energy efficiency to encompass design principles, cross-sector collaboration, and sectors such as the bioeconomy and recycling, in addition to the more recent incorporation of digital technologies and consumer-focused strategies. Based on the analysis, the concept of Circular and Sustainable Business Model Innovation (CSIBI) is proposed, integrating the triad and systematizing its conceptual basis. The future research agenda covers strategies and metrics for sustainable circularity, as well as the role of digital technologies, governance, and human factors, providing guidance to consolidate the field. This framework contributes to the advancement of new research, strengthens the adoption of business practices in the transition to more circular and sustainable business models, and provides input for public policymakers, integrating the principles of the circular economy, innovation, and sustainable business models.

Carbon fluxes and partitioning in Eucalyptus and Pinus plantations across a climatic gradient in Brazil - Fernanda Leite Cunha; Otávio Camargo Campoe; Cléber Rodrigo de Souza; Isaira Leite & Lopes; Yann Nouvellon; Timothy Albaugh; David R. Carter; Rafael Rubilar; Isabel Deliberari; Rachel Cook; Joannès Guillemot; Guerric Le Maire; et al. (Agricultural and Forest Meteorology, 2026)

A comprehensive genome-wide association study and genomic prediction in olive flounder for assessing disease resistance to Enteromyxum leei - Gaeun Kim; D.S. Liyanage; Jeongeun Kim; Jihun Lee; Y.K. Kodagoda; H.A.C.R. Hanchapola; M.A.H. Dilshan; D.C.G. Rodrigo; G.A.N.P. Ganepola; Sukkyoung Lee; David B. Jones; Cecile Massault; et al. (Fish & Shellfish Immunology, 2026)

Cultivar plasticity in temperate fruit trees across the Mediterranean region: Different combinations of chill and heat lead to dormancy release - Alvaro Delgado; David Ruiz; Javier Rodrigo; Eike Luedeling; Eduardo Fernandez; Hajar Mojahid; Brenda I. Guerrero; M. Engracia Guerra; Nestor Santolaria; Patricia Irisarri; Jose A. Egea; Lars Caspersen; et al. (European Journal of Agronomy, 2026)

Impacts of rotation, tillage, cover cropping, and drainage on soil health in soybean-based cropping systems: Evidence from 4–50-year trials across the US - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Chad D. Lee; David Jordan; Hanna J. Poffenbarger; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Agriculture, Ecosystems & Environment, 2026)

Design and performance of the Low-Energy Module for the Ziré instrument on the NUSES mission: A compact spectrometer for low-energy particles in space high-radiation environments - Muhammd Abdullahi; Roberto Aloisio; Francesco Arneodo; Sindorjon Ashurov; Uygar Atalay; Felicia C.T. Barbato; Roberto Battiston; Mario Bertaina; Elisabetta Bissaldi; Denise Boncioli; Leonid Burmistrov; Franck Cadoux; et al. (Advances in Space Research, 2026)

Taxonomic update for the giant algal chloroviruses of the family Phycodnaviridae - Rodrigo A. L. Rodrigues; João Victor R. P. Carvalho; Lethícia R. Henriques; David D. Dunigan; James L. Van Etten (Archives of Virology, 2026)

The Missing Global South in Climate Change Biology: Towards Equitable Knowledge Inclusion for Effective Global Solutions - Wesley Dáttilo; Rodrigo Beas‐Luna; Alma Mendoza‐Ponce; Angela Nava‐Bolanos; Angela P. Cuervo‐Robayo; Carolina Ureta; Constantino Gonzalez‐Salazar; Cuauhtemoc Saenz‐Romero; Daniel Jimenez‐Garcia; David A. Prieto‐Torres; Eduardo Cuevas; Gabriela Castano‐Meneses; et al. (Global Change Biology, 2026)
Over the last decades, climate change biology has become a central field in global science, yet knowledge production and its inclusion in global strategies remain profoundly unequal. Our bibliometric analysis of over 580,000 records shows that ~80% of author affiliations come from Global North institutions, meaning that research agendas, theoretical frameworks, and priorities are still largely shaped outside the regions with the highest biodiversity and greatest vulnerability to climate change. This imbalance reflects structural and historical inequalities that limit the ability of Global South countries to conduct autonomous research and sustain long‐term monitoring. When research and funding originate abroad, local scientists are often excluded, leading to the loss of traditional knowledge, regional perspectives, and long‐term capacity building. These dynamics leave tropical and subtropical bioregions (generally in the Global South) underrepresented in global climate knowledge. To address this imbalance, we propose six actions: invest in infrastructure and monitoring, strengthen local research networks, link funding to capacity building, promote open and equitable data access, connect science with regional policies, and foster intersectoral collaboration. We argue that truly effective climate change biology must be global, equitable, and diverse.

Integrating machine learning into a fully coupled current-wave-sediment model: Characterizing particle size in the settling process in estuaries of the Great Barrier Reef, Australia - Ziyu Xiao; Daniel N. Livsey; Thomas Schroeder; David Blondeau-Patissier; Rodrigo Santa Cruz; Jiasheng Su; Dehai Song; Xiao Hua Wang; Geoffrey Carlin; Andrew D.L. Steven; Joseph R. Crosswell (Ocean Modelling, 2025)

Growth rate and finishing system alter beef color and early postmortem metabolism in Bos indicus crossbred cattle - Juan F. Morales Gómez; Patricia M. Ramos; Mariane Beline; Daniel S. Antonelo; Bruna Pavan; Rodrigo S. Goulart; Laila T. Kirkpatrick; David E. Gerrard; Saulo L. Silva (Meat Science, 2025)

Multi-trait GWAS for growth under contrasting thermal rearing conditions in rainbow trout (Oncorhynchus mykiss) - Jousepth Gallardo-Hidalgo; David A. Tapia; Baltasar F. Garcia; Rodrigo Marin-Nahuelpi; Pablo Cáceres; Liane N. Bassini; Vito A. Mastrochirico-Filho; Carolina Araya; José M. Yáñez (Molecular Genetics and Genomics, 2025)

Contrasting responses to climate change – predicting bloom of major temperate fruit tree species in the Mediterranean region and Central Europe - Lars Caspersen; Katja Schiffers; Antonio Picornell; Jose A. Egea; Alvaro Delgado; Adnane El Yaacoubi; Haïfa Benmoussa; Javier Rodrigo; Erica Fadón; Mehdi Ben Mimoun; Mohamed Ghrab; Ossama Kodad; et al. (Agricultural and Forest Meteorology, 2025)

Nearly Synchronous Speciation in the Mexican Highlands: Did the Juniperus deppeana Complex Diverge Under Peripatry? - Rodrigo Martínez de León; Melania Vega; David S. Gernandt; Juan Pablo Jaramillo‐Correa; Alejandra Moreno‐Letelier (Molecular Ecology, 2025)
Speciation is a central focus in evolutionary biology, yet the processes driving diversification in montane regions remain incompletely understood. The Mexican highlands, a hotspot of conifer diversity characterised by complex topography and pronounced climatic heterogeneity, offer a unique setting to study these dynamics. Here, we investigated the genetic and taxonomic diversity within the Juniperus deppeana species complex, a group that exhibits notable cryptic variation. Using multiple species delimitation methods and Approximate Bayesian Computation, we identified at least four distinct evolutionary lineages that diverged largely without gene flow, likely influenced by geographic barriers and climatic differences. Our study enhances the understanding of how environmental heterogeneity and historical factors contribute to lineage diversification in montane conifers, offering new insights into the remarkable origins and resilience of biodiversity in the Mexican highlands. We present the J. deppeana complex as a compelling example of peripatric speciation and a valuable model system for understanding conifer diversification.

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

Spatial and Temporal Size Distribution of Swordfish ( Xiphias gladius ) in the Atlantic Ocean: Implications for Conservation and Management - Daniela Rosa; Michael Schirripa; Kyle Gillespie; David Macías; Rodrigo Forselledo; Bruno Mourato; Mikihiko Kai; Freddy Arocha; Nan-Jay Su; Sven Kerwath; Laurent Bahou; Luigi Pappalardo; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Insights into the 100 largest European surface ozone episodes during spring–summer 2003–2022 - Tahimy Fuentes-Alvarez; Carlos Ordóñez; Ricardo García-Herrera; David Barriopedro; Rodrigo Crespo-Miguel; Miguel M. Lima (Science of The Total Environment, 2025)

Simulating Carbon Mineralization at Pore Scale in Capillary Networks of Digital Rock - David A. Lazo Vasquez; Jaione Tirapu Azpiroz; Rodrigo Neumann Barros Ferreira; Ronaldo Giro; Manuela Fernandes Blanco Rodriguez; Matheus Esteves Ferreira; Mathias B. Steiner (Transport in Porous Media, 2025)
Predicting the geometrical evolution of the pore space in geological formations due to fluid–solid interactions has applications in reservoir engineering, oil recovery, and geological storage of carbon dioxide. However, modeling frameworks that combine fluid flow with physical and chemical processes at a rock’s pore scale are scarce. Here, we report a method for modeling a rock’s pore space as a network of connected capillaries and to simulate the capillary diameter modifications caused by reactive flow processes. Specifically, we model mineral erosion, deposition, dissolution, and precipitation processes by solving the transport equations iteratively, computing diameter changes within each capillary of the network simultaneously. Our automated modeling framework enables simulations with digital rock samples as large as (1.125 mm) $$^3$$ 3 having 125 $$×$$ × 10 $$^6$$ 6 voxels, within seconds of CPU time per iteration. As an application of the computational method, we have simulated brine injection and calcium carbonate precipitation in sandstone. For quantitatively comparing simulation results obtained with models predicting either a constant or a flow rate-dependent precipitation, we track the time-dependent capillary diameter distribution as well as the permeability of the connected pore space. For validation and reuse, we have made the automated simulation workflow, the reactive flow model library, and the digital rock samples available in public repositories.

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Outcomes Following Second Allogeneic Stem Cell Transplant for Graft Failure or Poor Graft Function: A Single Centre Experience - Jowon L. Kim; Moss A. Bruton Joe; Shanee Chung; Hannah Cherniawsky; Donna L. Forrest; Florian Kuchenbauer; Deepesh Lad; Stephen H. Nantel; Sujaatha Narayanan; Thomas J. Nevill; Judith Rodrigo; David Sanford; et al. (Stem Cell Reviews and Reports, 2025)

Complications of applying approximate entropy to heart rate variability to locate optimal complexity in children with attention deficit hyperactivity disorder - David M. Garner; Tatiana Dias de Carvalho; Rubens Wajnsztejn; Luiz Carlos Marques Vanderlei; Vitor Engracia Valenti; Luiz Carlos de Abreu; Rodrigo Daminello Raimundo (European Journal of Applied Physiology, 2025)

Endophytic Streptomyces sp. N2A protects soybean against fungal diseases through two distinct mechanisms - David L. Villafañe; Rodrigo A. Maldonado; Eduardo Rodríguez; María Amalia Chiesa (BioControl, 2025)

Decapod community composition is seasonally driven by different environmental factors in an estuarine-coastal gradient (Eastern Brazil) - Ronaldo R. Oliveira-Filho; Mariana Antunes; Joelson Musiello-Fernandes; Rodrigo Guéron; Helen Audrey Pichler; Ciro Colodetti Vilar; Fernando L. Mantelatto; Jean-Christophe Joyeux; Julien Chiquieri; Maurício Hostim-Silva; David Bauman (Regional Studies in Marine Science, 2025)

Genome-wide association mapping of scuticociliatosis resistance in a vaccinated population of olive flounder (Paralichthys olivaceus) - Yasara Kavindi Kodagoda; Gaeun Kim; D.S. Liyanage; W.K.M. Omeka; Cheonguk Park; Jeongeun Kim; Ji Hun Lee; H.A.C.R. Hanchapola; M.A.H. Dilshan; D.C.G. Rodrigo; David B. Jones; Cecile Massault; et al. (Fish & Shellfish Immunology, 2025)

Artificial reef site-specific design under upwelling favourable winds: Ría de Ares-Betanzos (NW Iberian Peninsula) - Rodrigo Carballo; Iván López; David Mateo Fouz; María Isabel Lamas; Luis Carral (Estuarine, Coastal and Shelf Science, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Soybean yield response to management practices (4–40 years) and soil health parameters - Tatiane Severo Silva; Lindsay Chamberlain Malone; Matthew D. Ruark; Spyridon Mourtzinis; Chad D. Lee; David Jordan; Herman J. Kandel; Jeremy Ross; John M. Gaska; Joseph G. Lauer; Laura E. Lindsey; Maninder Pal Singh; et al. (Field Crops Research, 2025)

Bird–window collisions: A comprehensive dataset for the Neotropical region - Augusto João Piratelli; Bianca Costa Ribeiro; Wesley Dáttilo; Luis‐Bernardo Vázquez; Anelisa Ferreira de Almeida Magalhães; Edna Maria Gomes Cavalcante; Eric Silva; Giovanna Viana Cruz; Gisele Regina Ruy; Juliana Laurito Summa; Júlia Milan; Leila Pedrosa; et al. (Ecology, 2025)
Our primary objective was to compile a comprehensive dataset on bird–window collisions throughout the Neotropical region, including both published and unpublished sources. On May 12, 2020, we extensively disseminated invitations to provide data via email and social media platforms. By providing a template worksheet, we required standardized information from collaborators to complete and register their data. To better understand how these data were acquired (e.g., incidental observations and systematic procedures), we sent out a survey to all collaborators. We established rigorous validation criteria for data inclusion and conducted thorough curation procedures to ensure accuracy. After the filtering process, we compiled a total of 4103 bird–window collision reports. These came from 11 Neotropical countries, dating from 1946 to 2020, and revealing distinct regional patterns and potential seasonal patterns. The five most frequent orders were Passeriformes (2451), Columbiformes (520), Apodiformes (377), Psittaciformes (202), and Piciformes (186). Data on bird–window collisions were collected through a local specific systematic protocol (1419), by chance (1252), by government agencies (742), and by other approaches (632), while a few reports were collected by unknown procedures (58). The volume of records across months in our dataset suggests that there may be temporal patterns, with peaks: the first one in March–April and the second one in October–November, which seem to align with the major migration and reproduction seasons. This dataset represents the first comprehensive effort in the Neotropical region focused on bird–window collision data, providing valuable insights for further scientific advancements and conservation policies. The data are free from copyright or proprietary restrictions. Please cite this data paper when using the data in publications or scientific presentations.

Impact of hydroethanolic extracts from Guaco leaves (Mikania glomerata Sprengel) on mechanical properties and bioactivities of gelatin-based bioactive films - David Willian Bertan; Luciana Ribeiro da Silva Lima; Paula Benoso; Rodrigo Vinicius Lourenço; Ana Mônica Quinta Barbosa Bittante; Andresa Gomes; Izabel Cristina Freitas Moraes; Mariana Simões Larraz Ferreira; Paulo José do Amaral Sobral (Food and Bioproducts Processing, 2025)

Multi-loaded PLGA microspheres as neuroretinal therapy in a chronic glaucoma animal model - Alba Aragón-Navas; Maria Jesus Rodrigo; Inés Munuera; David García-Herranz; Manuel Subías; Pilar Villacampa; Julián García-Feijoo; Luis Pablo; Elena Garcia-Martin; Rocio Herrero-Vanrell; Irene Bravo-Osuna (Drug Delivery and Translational Research, 2025)
This work focused on the co-encapsulation and simultaneous co-delivery of three different neuroprotective drugs in PLGA (poly(lactic-co-glycolic acid) microspheres for the treatment of glaucoma. For formulation optimization, dexamethasone (anti-inflammatory) and ursodeoxycholic acid (anti-apoptotic) were co-loaded by the solid-in-oil-in-water emulsion solvent extraction-evaporation technique as a first step. The incorporation of a water-soluble co-solvent (ethanol) and different amounts of dexamethasone resulted critical for the encapsulation of the neuroprotective agents and their initial release. The optimized formulation was obtained with 60 mg of dexamethasone and using an 80:20 dichloromethane:ethanol ratio. In the second step in the microencapsulation process, the incorporation of the glial cell line-derived neurotrophic factor (GDNF) was performed. The final prototype showed encapsulation efficiencies for each component above 50% with suitable properties for long-term application for at least 3 months. Physicochemical studies were performed by SEM, TEM, DSC, XRD, and gas chromatography. The evaluation of the kinetic release by the Gallagher-Corrigan analysis with Gorrasi correction helped to understand the influence of the co-microencapsulation on the delivery of the different actives from the optimized formulation. The final prototype was tested in a chronic glaucoma animal model. Rats received two intravitreal injections of the neuroprotective treatment within a 24-week follow-up study. The proposed formulation improved retinal ganglion cell (RGC) functionality examined by electroretinography. Also, it was able to maintain a neuroretinal thickness similar to that of healthy animals scanned by in vivo optical coherence tomography, and a higher RGC count on histology compared to glaucomatous animals at the end of the study. Graphical Abstract

Feeding rate for newly weaned tambaqui (Colossoma macropomum) juveniles in a recirculating aquaculture system - Bruno José Corecha Fernandes Eiras; Paola Fabiana Fazzi Gomes; Debora Sayumi Doami Melo; Jhonas Warlenson Palheta Nobre; Helen Cristiane Araújo Souza; Marcela Cardoso Sena; Joane Natividade; Igor Hamoy; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; André Luiz Alves de Sá; Rodrigo Takata; et al. (Animal Feed Science and Technology, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Resilient plants, sustainable future - Seung Y. Rhee; Daniel N. Anstett; Edgar B. Cahoon; Alejandra A. Covarrubias-Robles; Eric Danquah; Natalia Dudareva; Hiroshi Ezura; Kadeem J. Gilbert; Rodrigo A. Gutiérrez; Michelle Heck; David B. Lowry; Ron Mittler; et al. (Trends in Plant Science, 2025)

Toxicity of essential oils on Callosobruchus maculatus (Fabr., 1775) in grains of Vigna unguiculata - Ozael David Valério da Silva; Paulo Roberto Ramalho Silva; Leticia Rodrigues da Silva; Rodrigo de Carvalho Brito; Kamilla de Andrade Dutra; Daniela Maria do Amaral Ferraz Navarro; Douglas Rafael e Silva Barbosa; Solange Maria de França (Journal of Plant Diseases and Protection, 2025)

Long‐haul flights and migratory routes of a nectar‐feeding bat - Theresa M. Laverty; Debbie C. Buecher; David C. Dalton; Mallory L. Davies; Fernando Gual‐Suárez; Paul A. Heady; Rodrigo A. Medellín; Mayra C. Ordóñez‐García; Samara Pérez‐Harp; A. Nayelli Rivera‐Villanueva; Brandi D. Stevenson; Kathryn E. Stoner; et al. (Ecology, 2025)

miR-512-3p as a Potential Biomarker of Poor Outcome in Pediatric Medulloblastoma - Carolina Alves Pereira Corrêa; Pablo Shimaoka Chagas; Mirella Baroni; Augusto Faria Andrade; Rosane Gomes de Paula Queiroz; Veridiana Kiill Suazo; Gustavo Alencastro Veiga Cruzeiro; Paola Fernanda Fedatto; David Santos Marco Antonio; Silvia Regina Brandalise; José Andres Yunes; Rodrigo Alexandre Panepucci; et al. (The Cerebellum, 2025)

Oreochromicin-2 shows antimicrobial and immunostimulant effect against respiratory pathogens in pigs - Liliana Basabe-Tuero; Lázara Ayala; Ivette Espinosa; Yeleiny Machín; Liany Coto; Carlos Duarte; Soraya Piloto; Antonio Morales; Osmany Rodrigo; David Diago; Iliana Sosa; Mario Pablo Estrada; et al. (Research in Veterinary Science, 2025)

Comparative economic, energy, and environmental analysis of fuel cell and electric eVTOL systems: Case study of Iberian Peninsula - Néstor Velaz-Acera; Rodrigo Ruiz-Marín; David Borge-Diez (Journal of Cleaner Production, 2025)

Sea turtles in the Atlantic and Indian Oceans, a step towards understanding bycatch and management of these species in tuna fisheries - Andrés Domingo; José Carlos Baéz; Philip Miller; Denham Parker; María Lourdes Ramos; Philippe S. Sabarros; Craig Brown; Juan Antonio Camiñas; Rui Coelho; Rodrigo Forselledo; Fernando Niemeyer Fiedler; Bruno Giffoni; et al. (Biological Conservation, 2025)

Diet and food availability of the critically endangered pygmy raccoon (Procyon pygmaeus) - Sofía Ana Lucrecia Lara-Godínez; David Valenzuela-Galván; Alberto González-Romero; Alfredo D. Cuarón; Vinicio J. Sosa; Rodrigo Alejandro Hernández-Cárdenas (Mammalian Biology, 2025)

LandFrag : A Dataset to Investigate the Effects of Forest Loss and Fragmentation on Biodiversity - Thiago Gonçalves‐Souza; Maurício Humberto Vancine; Nathan J. Sanders; Nick M. Haddad; Lucas Cortinhas; Anne Lene T. O. Aase; Willian Moura de Aguiar; Marcelo Adrian Aizen; Víctor Arroyo‐Rodríguez; Arturo Baz; Maíra Benchimol; Enrico Bernard; et al. (Global Ecology and Biogeography, 2025)
Motivation The accelerated and widespread conversion of once continuous ecosystems into fragmented landscapes has driven ecological research to understand the response of biodiversity to local (fragment size) and landscape (forest cover and fragmentation) changes. This information has important theoretical and applied implications, but is still far from complete. We compiled the most comprehensive and updated database to investigate how these local and landscape changes determine species composition, abundance and trait diversity of multiple taxonomic groups in forest fragments across the globe. Main Types of Variables Contained We gathered data for 1472 forest fragments, providing information on the abundance and composition of 9154 species belonging to vertebrates, invertebrates, and plants. For 2703 of these species, we obtained more than 20 functional traits. We provided the spatial location and size of each fragment and metrics of landscape composition and configuration. Spatial Location and Grain The dataset includes 1472 forest fragments sampled in 121 studies from all continents except Antarctica. Most datasets (77%) are from tropical regions, 17% are from temperate regions, and 6% are from subtropical regions. Species abundance and composition were collected at the plot or fragment scale, whereas the landscape metrics were extracted with buffer size ranging from a radius of 200–2000 m. Time Period and Grain Data on the abundance of species and community composition were collected between 1994 and 2022, and the landscape metrics were extracted from the same year that a given study collected the abundance and composition data. Major Taxa and Level of Measurement The studied organisms included invertebrates (Arachnida, Insecta and Gastropoda; 41% of the datasets), vertebrates (Amphibia, Squamata, Aves and Mammalia; 44%), and vascular plants (19%), and the lowest level of identification was species or morphospecies. Software Format The dataset and code can be downloaded on Zenodo or GitHub.

On Performance of Data Models and Machine Learning Routines for Simulations of Casting Processes - Amir M. Horr; Rodrigo Gómez Vázquez; David Blacher (BHM Berg- und Hüttenmännische Monatshefte, 2025)
The performance of data models and their associated machine-learning (ML) routines for simulations of multi-physical continuous casting processes are scrutinised in this research contribution. Data science techniques have a growing impact on the optimisation and controlling of manufacturing processes by providing fast and real-time predictive-corrective tools. These techniques employ data analytics, data training/learning, and deterministic/statistical methods to create fast and real-time models to improve manufacturing processes. In this research work, data reduced models and ML routines are developed to predict the influence of various process parameters on direct chill casting processes. These data models represent the essential features of the multi-physical casting processes, while significantly reducing the simulation time and efforts. Hence, the computational fluid dynamics (CFD) simulations are initially used to create a comprehensive database where variations of major process parameters are considered using carefully sampled snapshot matrices. These matrices are employed to capture the most important aspects of the processing parameters including melt temperature, cooling and casting speed. Furthermore, the resulting data models are thoroughly examined for their accuracy and reliability using some selected design of experiments (DOEs).

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Land Use Change Consistently Reduces α‐ But Not β‐ and γ‐Diversity of Bees - Toby P. N. Tsang; A. A. Amado De Santis; Gabriela Armas‐Quiñonez; John S. Ascher; Eva Samanta Ávila‐Gómez; András Báldi; Kimberly M. Ballare; Mario V. Balzan; Weronika Banaszak‐Cibicka; Svenja Bänsch; Yves Basset; Adam J. Bates; et al. (Global Change Biology, 2025)
Land use change threatens global biodiversity and compromises ecosystem functions, including pollination and food production. Reduced taxonomic α‐diversity is often reported under land use change, yet the impacts could be different at larger spatial scales (i.e., γ‐diversity), either due to reduced β‐diversity amplifying diversity loss or increased β‐diversity dampening diversity loss. Additionally, studies often focus on taxonomic diversity, while other important biodiversity components, including phylogenetic diversity, can exhibit differential responses. Here, we evaluated how agricultural and urban land use alters the taxonomic and phylogenetic α‐, β‐, and γ‐diversity of an important pollinator taxon—bees. Using a multicontinental dataset of 3117 bee assemblages from 157 studies, we found that taxonomic α‐diversity was reduced by 16%–18% in both agricultural and urban habitats relative to natural habitats. Phylogenetic α‐diversity was decreased by 11%–12% in agricultural and urban habitats. Compared with natural habitats, taxonomic and phylogenetic β‐diversity increased by 11% and 6% in urban habitats, respectively, but exhibited no systematic change in agricultural habitats. We detected a 22% decline in taxonomic γ‐diversity and a 17% decline in phylogenetic γ‐diversity in agricultural habitats, but γ‐diversity of urban habitats was not significantly different from natural habitats. These findings highlight the threat of agricultural expansions to large‐scale bee diversity due to systematic γ‐diversity decline. In addition, while both urbanization and agriculture lead to consistent declines in α‐diversity, their impacts on β‐ or γ‐diversity vary, highlighting the need to study the effects of land use change at multiple scales.

FreshLanDiv : A Global Database of Freshwater Biodiversity Across Different Land Uses - Minghua Shen; Roel van Klink; Alban Sagouis; Danielle K. Petsch; Deborah Atieno Abong'o; Janne Alahuhta; Salman Abdo Al‐Shami; Laura Cecilia Armendáriz; Mi‐Jung Bae; Tiago Octavio Begot; Jerome Belliard; Jonathan Peter Benstead; et al. (Global Ecology and Biogeography, 2024)
Motivation Freshwater ecosystems have been heavily impacted by land‐use changes, but data syntheses on these impacts are still limited. Here, we compiled a global database encompassing 241 studies with species abundance data (from multiple biological groups and geographic locations) across sites with different land‐use categories. This compilation will be useful for addressing questions regarding land‐use change and its impact on freshwater biodiversity. Main Types of Variables Contained The database includes metadata of each study, sites location, sample methods, sample time, land‐use category and abundance of each taxon. Spatial Location and Grain The database contains data from across the globe, with 85% of the sites having well‐defined geographical coordinates. Major Taxa and Level of Measurement The database covers all major freshwater biological groups including algae, macrophytes, zooplankton, macroinvertebrates, fish and amphibians.

Identification of chemically altered cut marks: an experimental approach from Geometrics Morphometrics - David Rodríguez de la Fuente; Lloyd A. Courtenay; Darío Herranz-Rodrigo; Jose Yravedra; Antonio Pineda (Archaeological and Anthropological Sciences, 2024)
Cut marks are striae accidentally produced by the contact made between the edge of a cutting tool and bone surfaces by anthropogenic activity, presenting evidence of hominin carcass processing and behaviour, butchery activities or diet. Post-depositional processes can cause the alteration (chemical or mechanical) of bones surfaces, changing their composition and causing the modification of bone surfaces. Previous research has addressed the problem of chemical alteration from a qualitative perspective, resulting in the loss of all diagnostic characteristics of the cut marks affected by these processes. Geometrics Morphometrics has led to great progress in the study of cut marks from a quantitative perspective and can be useful for the study of altered cut marks. In this study, an experiment was carried out in which 36 cut marks were reproduced and chemically altered. These marks were scanned and digitized before and after each phase of alteration. They were analyzed metrically as well as using Geometric Morphometrics, in order to study the evolution of modifications to cut mark morphology during the experiment. Results show clear morphological differences between the different phases of alteration with altered cut marks presenting a general tendency towards a decrease in both the width and depth over time. Research of this type opens up a new path for the study of the chemical alteration of cut marks, as well as other striae, through the application of Geometric Morphometrics.

Reproductive phenology of the non-woody community in a seasonally dry tropical forest and woodland in northeastern Brazil - Sâmia Paula Santos Neves; Adelly Cardoso de Araujo Fagundes; Alexsandro Bezerra-Silva; Paulo Sérgio Neves dos Santos; David Rodrigo Rossatto; Lia d’Afonsêca Pedreira de Miranda; Ligia Silveira Funch (Journal of Arid Environments, 2024)

Synthetic, marine, light-driven, autotroph-heterotroph co-culture system for sustainable β-caryophyllene production - Wenchao Chen; Young-Kyoung Park; Lucie Studená; David Bell; Piotr Hapeta; Jing Fu; Peter J. Nixon; Rodrigo Ledesma-Amaro (Bioresource Technology, 2024)

Multi-million-year magmatic and hydrothermal activity is key to the formation of supergiant to behemothian porphyry copper deposits - Adrianna Luiza Virmond; Jörn-Frederik Wotzlaw; Rodrigo Rojas-Arancibia; David Selby; Cyril Chelle-Michou (Contributions to Mineralogy and Petrology, 2024)
Understanding the primary controls on mineral deposit formation and size is essential for sourcing the metals required by our ever-growing economy. The tonnage of porphyry copper deposits ranges five orders of magnitude but the key mechanisms and processes that modulate the size of these deposits remain enigmatic. Here, we investigate the behemothian deposits of the Chuquicamata Intrusive Complex (CIC) in northern Chile employing high-precision U–Pb and Re–Os geochronology. We resolve a complex long-lived magmatic-hydrothermal activity that lasted over 3.3 Myr. High-precision zircon petrochronology data indicate two distinct porphyry emplacement episodes, separated by 0.5 Myr, with the younger generation closely tied to the main intervals of hydrothermal mineralization. High-precision Re–Os molybdenite dates reveal a prolonged hydrothermal mineralization interval (> 2.5 Myr) that progressively migrated southwards within the CIC and continued after the end of the (apparent) magmatic activity. We show that the rate of copper precipitation varies little in nature (0.025–0.10 Mt/kyr) and is independent of the size of the deposit. Consistent with evidence from smaller deposits, our findings provide unprecedented evidence that copper endowment in porphyry copper deposits positively correlates with the timescales of magmatic and hydrothermal activity. Supergiant to behemothian deposits require multi-million-year magmatic-hydrothermal activity, linking the largest porphyry copper systems to a simple metric – the duration of magmatic-hydrothermal activity.

An assessment of potential interventions to reduce the totoaba illegal trade market - Rodrigo Oyanedel; Erendira Aceves‐Bueno; Lucia Davids; Miguel Ángel Cisneros‐Mata (Conservation Biology, 2024)
The illegal trade in totoaba ( Totoaba macdonaldi ) is causing adverse social, ecological, and economic impacts. This illegal activity is accelerating the overexploitation of totoaba and pushing the critically endangered vaquita ( Phocoena sinus ) closer to extinction. Despite extensive efforts to recover vaquita populations, scant attention has been given to the totoaba trade as an independent issue. As a result, data on the totoaba trade are limited, which hampers robust analyses and development of effective interventions to reduce illegal harvesting. We used a previously developed framework specifically designed to examine dynamics of illegal markets and guide measures to mitigate illegal use of totoaba. This framework separates markets into 3 analytical levels: characterization of participating actors (e.g., fishers, intermediaries); examination of how actors interact within the market (e.g., organization of supply chains); and assessment of the overall market dynamics that result from these interactions (e.g., factors determining price and quantity). We reviewed existing literature (108 initial articles) and interviewed key market actors, academics, and nongovernmental organization experts (14) to obtain data for this framework. Our findings offer an overview of the totoaba illegal market operation, highlighting intervention points (e.g., customs agents) and areas where additional information is required to decrease information gaps (e.g., US local market). We describe the structure and complexity of this market, emphasizing the influential role of organized crime in shaping its dynamics (e.g., controlling prices paid to fishers and stockpiling). By providing a systematic and in‐depth understanding of the market operation, we aimed to establish a benchmark for effective interventions and future research aimed at reducing uncertainties. Our results provide a crucial step toward addressing this critical issue and can help facilitate development of effective strategies to combat the illegal totoaba trade and promote biodiversity conservation more broadly.

Influence of trophic overlaps and trophic niche amplitude on microplastic intake of fish species in shallow areas of a neotropical coastal lagoon - David V. Dantas; Cristian I.R. Ribeiro; Leticia S.C. Ito; Ana P.T. Pezzin; Victória F. Silveira; Ana L.P. Cardozo; Eduardo Gentil; Isabel B. Monteiro; Sofia A. Ribeiro; Luciano Lorenzi; Rodrigo Machado (Science of The Total Environment, 2024)

Streptomyces N2A, an endophytic actinobacteria that promotes soybean growth and increases yield and seed quality under field conditions - David L. Villafañe; Rodrigo A. Maldonado; Julieta S. Bianchi; Daniel Kurth; Hugo Gramajo; María Amalia Chiesa; Eduardo Rodríguez (Plant Science, 2024)

Terrestrial and Martian space weather: A complex systems approach - Abraham Chian; Rodrigo Miranda; Cesar Bertucci; Xóchitl Blanco-Cano; Joe Borovsky; Sergio Dasso; Ezequiel Echer; Adriane Franco; Kirolosse M. Girgis; J. Américo González-Esparza; Tohru Hada; Hiroshi Hasegawa; et al. (Journal of Atmospheric and Solar-Terrestrial Physics, 2024)

Evapotranspiration in the Amazon Basin: Couplings, hydrological memory and water feedback - Paulo Rodrigo Zanin; David Pareja-Quispe; Jhan-Carlo Espinoza (Agricultural and Forest Meteorology, 2024)

Association parameters for Cubic-Plus-Association equation of state determined by molecular dynamics and Petroleomics: Prediction of asphaltene precipitation - Ivan Moncayo-Riascos; Juan David Aristizábal; Oscar Ramírez-Jaramillo; Fernando A. Rojas-Ruiz; Jorge A. Orrego-Ruiz; Rodrigo Torres-Sáez; Cristiam Cundar; Wilson Cañas-Marín; Raul Osorio (Fuel, 2024)

Dietary effect of multi-strain prebiotics and probiotics on growth, hemato-biochemical parameters, intestinal histomorphometry, and resistance to hypoxia in juvenile tambaqui (Colossoma macropomum) - Rafael José Furtado Souza; Edilson Rodrigues Matos; Aldry Lorran da Silva Souza; Paola Fabiana Fazzi-Gomes; Nuno Filipe Alves Correia de Melo; Marco Shizuo Owatari; Glauber David Almeida Palheta; Rodrigo Takata; Fabio Carneiro Sterzelecki (Veterinary Research Communications, 2024)

Human habitat modification, not apex scavenger decline, drives isotopic niche variation in a carnivore community - Olivia Bell; Menna E. Jones; Manuel Ruiz-Aravena; David G. Hamilton; Sebastien Comte; Rowena Hamer; Rodrigo K. Hamede; Jason Newton; Stuart Bearhop; Robbie A. McDonald (Oecologia, 2024)
Top carnivores can influence the structure of ecological communities, primarily through competition and predation; however, communities are also influenced by bottom-up forces such as anthropogenic habitat disturbance. Top carnivore declines will likely alter competitive dynamics within and amongst sympatric carnivore species. Increasing intraspecific competition is generally predicted to drive niche expansion and/or individual specialisation, while interspecific competition tends to constrain niches. Using stable isotope analysis of whiskers, we studied the effects of Tasmanian devil Sarcophilus harrisii declines upon the population- and individual-level isotopic niches of Tasmanian devils and sympatric spotted-tailed quolls Dasyurus maculatus subsp. maculatus. We investigated whether time since the onset of devil decline (a proxy for severity of decline) and landscape characteristics affected the isotopic niche breadth and overlap of devil and quoll populations. We quantified individual isotopic niche breadth for a subset of Tasmanian devils and spotted-tailed quolls and assessed whether between-site population niche variation was driven by individual-level specialisation. Tasmanian devils and spotted-tailed quolls demonstrated smaller population-level isotopic niche breadths with increasing human-modified habitat, while time since the onset of devil decline had no effect on population-level niche breadth or interspecific niche overlap. Individual isotopic niche breadths of Tasmanian devils and spotted-tailed quolls were narrower in human-modified landscapes, likely driving population isotopic niche contraction, however, the degree of individuals’ specialisation relative to one another remained constant. Our results suggest that across varied landscapes, mammalian carnivore niches can be more sensitive to the bottom-up forces of anthropogenic habitat disturbance than to the top-down effects of top carnivore decline.

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Strategies for fungicide application based on the yield response of common bean genotypes under El Niño-Southern Oscillation (ENSO) - Alexandre Bryan Heinemann; Patrícia Valle Pinheiro; David Henriques da Matta; Luís Fernando Stone; Pedro Araújo Pietrafesa; William Rafael Ribeiro; Rodrigo Yoiti Tsukahara; Hélio Antônio Wood Joris (European Journal of Agronomy, 2024)

An objective procedure for rainy season onset and withdrawal dates over the Mexico Valley Basin - Rodrigo Muñoz-Sanchez; Paulina Ordoñez; David Gallego; Carlos A. Ochoa-Moya (Theoretical and Applied Climatology, 2024)
This work aims to define a procedure to declare rainy season onset and withdrawal dates for the Mexico Valley Basin, located in central Mexico. The onset/withdrawal is obtained using only precipitation for the study period 1981–2020. The onset is defined as the first day, between May 1st and July 15th, of the first 20 consecutive days having a 20-day average precipitation over the Basin of at least 2.5 mm/day. The withdrawal is defined as the last day, between September 1st and November 15th, of the last 20 consecutive days having a 20-day average precipitation of at least 1.7 mm/day. The mean onset is June 6th, with a standard deviation of 14.3 days; the mean withdrawal date is October 15th, with a standard deviation of 16.1 days; and the average length of the rainy season is 131 days, with a standard deviation of 22.7 days. These criteria maximize the precipitation change slope during onset/withdrawal. We categorized pre- and post-onset/withdrawal periods to investigate mean circulation characteristic changes. Besides a stark increase (decrease) in rainfall over the Basin during onset (withdrawal), we found that vertically integrated moisture transport over the Caribbean Low-Level Jet core region increases (decreases). The onset/withdrawal dates derived show interannual trends, while a late (early) withdrawal is associated with a positive (negative) ENSO Index, and a strong (weak) Caribbean Low Level Jet (CLLJ) is associated with a late (early) onset.

Growth, survival, and myogenic gene expression in the post-larvae of Colossoma macropomum provisioned with Artemia nauplii - Debora Sayumi Doami Melo; André Luiz Alves de Sá; Sávio Lucas de Matos Guerreiro; Joane Natividade; Paola Fabiana Fazzi Gomes; Rodrigo Takata; Ednaldo da Silva Filho; Glauber David Almeida Palheta; Nuno Filipe Alves Correia de Melo; Fabio Carneiro Sterzelecki; Igor Hamoy (Fish Physiology and Biochemistry, 2024)

Investigation of Cerebral Mitochondrial Injury in a Porcine Survivor Model of Carbon Monoxide Poisoning - Constantine D. Mavroudis; Alistair Lewis; John C. Greenwood; Matthew Kelly; Tiffany S. Ko; Rodrigo M. Forti; Samuel S. Shin; Frances S. Shofer; Johannes K. Ehinger; Wesley B. Baker; Todd J. Kilbaugh; David H. Jang (Journal of Medical Toxicology, 2024)

Groundwater is a hidden global keystone ecosystem - Mattia Saccò; Stefano Mammola; Florian Altermatt; Roman Alther; Rossano Bolpagni; Anton Brancelj; David Brankovits; Cene Fišer; Vasilis Gerovasileiou; Christian Griebler; Simone Guareschi; Grant C. Hose; et al. (Global Change Biology, 2024)
Groundwater is a vital ecosystem of the global water cycle, hosting unique biodiversity and providing essential services to societies. Despite being the largest unfrozen freshwater resource, in a period of depletion by extraction and pollution, groundwater environments have been repeatedly overlooked in global biodiversity conservation agendas. Disregarding the importance of groundwater as an ecosystem ignores its critical role in preserving surface biomes. To foster timely global conservation of groundwater, we propose elevating the concept of keystone species into the realm of ecosystems, claiming groundwater as a keystone ecosystem that influences the integrity of many dependent ecosystems. Our global analysis shows that over half of land surface areas (52.6%) has a medium‐to‐high interaction with groundwater, reaching up to 74.9% when deserts and high mountains are excluded. We postulate that the intrinsic transboundary features of groundwater are critical for shifting perspectives towards more holistic approaches in aquatic ecology and beyond. Furthermore, we propose eight key themes to develop a science‐policy integrated groundwater conservation agenda. Given ecosystems above and below the ground intersect at many levels, considering groundwater as an essential component of planetary health is pivotal to reduce biodiversity loss and buffer against climate change.

Tailoring the pore architecture and crystalline structure of UiO-66 for the selective adsorption of anionic species in aqueous media - Hugo G. Palhares; Alice G. Leonel; Rodrigo L. Oréfice; Ricardo O. Correia; David Riassetto; Michel Langlet; Manuel Houmard; Eduardo H.M. Nunes (Environmental Nanotechnology, Monitoring & Management, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Predator‐induced defences under tropicalisation: A biogeographic approach - Phillip B. Fenberg; Rodrigo Beas‐Luna; Boris Igić; Moira A. MacLean; David A. Paz‐García; Peter T. Raimondi; Jacqueline L. Sones; Karolina M. Zarzyczny; Eric Sanford (Journal of Biogeography, 2023)
Aim The biogeography of predator‐induced defences is an understudied area of predator–prey dynamics. Range overlap with predators that induce the response and local demographics (e.g., prey abundances) are likely to be important factors for determining the biogeographic distribution of induced defences within species. However, with climate warming, range‐expanding warm‐water predators are increasingly preying upon temperate species. This is a consequence of a wider phenomenon known as tropicalisation. We aim to determine: (i) if individuals of a temperate barnacle with induced defences (‘bent morphs’) are primarily present where they co‐occur with range‐expanding warm‐water predators (muricid snails) and, (ii) if bent morphs are size‐structured within populations. Location North‐eastern Pacific rocky intertidal zone (~26–40° N). Taxon Tetraclita rubescens (Nilsson‐Cantell, 1931), Balanomorpha. Methods We use photoquadrats from sites across the range of T. rubescens to determine the biogeographic distribution of populations with bent morphs and to assess size‐structure. We use a combination of field surveys, literature, and museum occurrences to assess range overlap between cool and warm‐water predators of T. rubescens and their association with populations with bent morphs and abundance patterns of T. rubescens . Results Bent morphs are commonly found within the equatorward portion of the species' range (where abundances are highest), in populations overlapping with range‐expanding warm‐water predators. Bent morphs primarily occur within the smaller size classes. Main conclusions To be partly resilient to the effects of tropicalisation, temperate prey must acclimatise/adapt to altered predator–prey dynamics. Predator‐induced defences are one way to do this. We show that bent morphs within a temperate prey species ( T. rubescens ) are largely restricted to populations that overlap with large‐bodied and range‐expanding warm‐water predators. This is evidence for the partial resilience of T. rubescens to tropicalisation and provides the rationale for further exploration of the eco‐evolutionary consequences of tropicalisation in this study system and others.

Locomotion behavior testing as a complementary tool in Collembola avoidance assays with neurotoxic insecticides - Felipe Ogliari Bandeira; Jéssica Karolayne Tina; Paulo Roger Lopes Alves; Vitor Pereira Vaz; Rodrigo Costa Puerari; Philippe Juneau; David Dewez; William Gerson Matias (Environmental Science and Pollution Research, 2023)

A novel 3D-printed graphite/polylactic acid sensor for the electrochemical determination of 2,4,6-trinitrotoluene residues in environmental waters - Gilvana P. Siqueira; Diele A.G. Araújo; Lucas V. de Faria; David L.O. Ramos; Tiago A. Matias; Eduardo M. Richter; Thiago R.L.C. Paixão; Rodrigo A.A. Muñoz (Chemosphere, 2023)

Electrification of steam cracking as a pathway to reduce the impact of the petrochemical industry on climate change - Oleksii Mynko; Mike Bonheure; Ismaël Amghizar; David J. Brown; Lin Chen; Guy B. Marin; Rodrigo Freitas de Alvarenga; Didem Civancik Uslu; Jo Dewulf; Kevin M. Van Geem (Journal of Cleaner Production, 2023)

Bearing capacity of shallow foundations on Florida limestone: A study of single layer and rock-over-sand subsurface - Kunyu Yang; Michael McVay; Thai Nguyen; Kaiqi Wang; Xiaoyu Song; Scott Wasman; Michael Rodgers; David Horhota; Rodrigo Herrera (Computers and Geotechnics, 2023)

Dirofilaria immitis in pet dogs from the metropolitan area of the Colombian Caribbean - Maria A. Badillo-Viloria; Ignacio García-Bocanegra; Rodrigo J. de Lavalle-Galvis; Remigio Martínez; Steffania de la Rosa-Jaramillo; Adriana Castillo-Castañeda; Juan D. Ramírez; David Cano-Terriza (Comparative Immunology, Microbiology and Infectious Diseases, 2023)

Amazonian earthworm biodiversity is heavily impacted by ancient and recent human disturbance - Ana C. Conrado; Wilian C. Demetrio; David W.G. Stanton; Marie L.C. Bartz; Samuel W. James; Alessandra Santos; Elodie da Silva; Talita Ferreira; Agno N.S. Acioli; Alexandre C. Ferreira; Lilianne S. Maia; Telma A.C. Silva; et al. (Science of The Total Environment, 2023)

Developing New Scales of Personal Food Security - Rodrigo Aranda; David C. Ribar (Journal of the Academy of Nutrition and Dietetics, 2023)

Estimation of genetic parameters for the tick and hemoparasite burden in Angus cattle - Gabriela David; Cherlynn Daniela da Silva Arce; Francisco Ribeiro de Araujo Neto; Lúcia Galvão de Albuquerque; Rodrigo Giglioti; Cíntia Hiromi Okino; Luciana Correia de Almeida Regitano; Márcia Cristina de Sena Oliveira; Henrique Nunes de Oliveira (Tropical Animal Health and Production, 2023)

Expression and localization of vascular endothelial growth factor and its receptors in the pig uterus during peri-implantation and determination of the in vitro effect of the angiogenesis inhibitor SU5416 on VEGF system expression - Rodrigo González López; David Alejandro Contreras Caro del Castillo; Griselda Valdez Magaña; Rosa Elena Sarmiento Silva; Francisco Ernesto Martínez Castañeda; María Elena Trujillo Ortega (Theriogenology, 2023)

A firebreak placement model for optimizing biodiversity protection at landscape scale - Jaime Carrasco; Rodrigo Mahaluf; Fulgencio Lisón; Cristobal Pais; Alejandro Miranda; Felipe de la Barra; David Palacios; Andrés Weintraub (Journal of Environmental Management, 2023)

Co-designing a multi-criteria approach to ranking hazards to and from Australia’s emerging offshore blue economy - Mischa P. Turschwell; Christopher J. Brown; Myriam Lacharité; Jess Melbourne-Thomas; Keith R. Hayes; Rodrigo H. Bustamante; Jeffrey M. Dambacher; Karen Evans; Pedro Fidelman; Darla Hatton MacDonald; Ingrid Van Putten; Graham Wood; et al. (Environmental Science & Policy, 2023)

Towards building a unified adsorption model for goethite based on direct measurements of crystal face compositions: I. Acidity behavior and As(V) adsorption - Rodrigo J. Martínez; Mario Villalobos; Alan U. Loredo-Jasso; América Xitlalli Cruz-Valladares; Arturo Mendoza-Flores; Hugo Salazar-Rivera; David Cruz-Romero (Geochimica et Cosmochimica Acta, 2023)

Amber and the Cretaceous Resinous Interval - Xavier Delclòs; Enrique Peñalver; Eduardo Barrón; David Peris; David A. Grimaldi; Michael Holz; Conrad C. Labandeira; Erin E. Saupe; Christopher R. Scotese; Mónica M. Solórzano-Kraemer; Sergio Álvarez-Parra; Antonio Arillo; et al. (Earth-Science Reviews, 2023)

The Prados del Cervunal morainic complex: Evidence of a MIS 2 glaciation in the Iberian Central System synchronous to the global LGM - Rosa M. Carrasco; Valentí Turu; Rodrigo L. Soteres; Javier Fernández-Lozano; Theodoros Karampaglidis; Ángel Rodés; Xavier Ros; Nuria Andrés; José Luis Granja-Bruña; Alfonso Muñoz-Martín; José Antonio López-Sáez; Regis Braucher; et al. (Quaternary Science Reviews, 2023)

Sex and the Estrous-Cycle Phase Influence the Expression of G Protein-Coupled Estrogen Receptor 1 (GPER) in Schizophrenia: Translational Evidence for a New Target - Francisco Eliclécio Rodrigues da Silva; Rafaela Carneiro Cordeiro; Camila N. de Carvalho Lima; Pablo Leal Cardozo; Germana Silva Vasconcelos; Aline Santos Monte; Lia Lira Olivier Sanders; Silvânia Maria Mendes Vasconcelos; David Freitas de Lucena; Breno Fiuza Cruz; Rodrigo Nicolato; Mary V. Seeman; et al. (Molecular Neurobiology, 2023)

Involvement of the excretory/secretory and surface-associated antigens of Dirofilaria immitis adult worms in the angiogenic response in an in-vitro endothelial cell model - Cristian David Cardona Machado; Claudia Alarcón-Torrecillas; Miguel Pericacho; Iván Rodríguez-Escolar; Elena Carretón; José Alberto Montoya-Alonso; Rodrigo Morchón (Veterinary Parasitology, 2023)

A geometric morphometrics and genetics characterization of Vanessa carye in an extreme elevational gradient in the Chilean Altiplano - Scott Escobar-Suárez; Amado Villalobos-Leiva; Alejandra Fabres; Rodrigo Órdenes-Clavería; Franco Cruz-Jofré; David Laroze; Margarita Correa; Moisés A. Valladares; Juan Sebastián D. Cáceres; Hugo A. Benítez (Zoologischer Anzeiger, 2023)

Novel clinical and immunological features associated with persistent post-acute sequelae of COVID-19 after six months of follow-up: a pilot study - Jiram Torres-Ruiz; Julieta Lomelín-Gascón; Jaquelin Lira Luna; Ana Sofia Vargas- Castro; Alfredo Pérez-Fragoso; Miroslava Nuñez-Aguirre; Beatriz Alcalá-Carmona; Abdiel Absalón-Aguilar; Jennifer T. Balderas-Miranda; José Luis Maravillas-Montero; Nancy R. Mejía-Domínguez; Carlos Núñez-Álvarez; et al. (Infectious Diseases, 2023)

Seafood consumers engagement in reducing environmental impacts from packaging - Cheila Almeida; Jara Laso; David Baptista de Sousa; Ronan Cooney; Paula Quinteiro; Neil Rowan; Ana Cláudia Dias; Eoghan Clifford; Rodrigo G. Reboredo; María Margallo; Maria Leonor Nunes; António Marques (Science of The Total Environment, 2023)

Climate change impacts on winter chill in Mediterranean temperate fruit orchards - Eduardo Fernandez; Hajar Mojahid; Erica Fadón; Javier Rodrigo; David Ruiz; Jose A. Egea; Mehdi Ben Mimoun; Ossama Kodad; Adnane El Yaacoubi; Mohamed Ghrab; José Egea; Haïfa Benmoussa; et al. (Regional Environmental Change, 2023)
Temperate trees require low temperatures during winter and subsequent warm conditions in early spring to flower and eventually bear fruit. Many parts of the Mediterranean region feature winters with low and sometimes marginal chill accumulation. To assess historic and future agroclimatic conditions for cultivating temperate trees (including almonds, pistachios, apricots, sweet cherries and apples), we mapped winter chill throughout this important growing region. We used on-site weather records (1974–2020) to calibrate a weather generator and produced data for historic and future scenarios. To broaden our analysis, we spatially interpolated chill for the whole Mediterranean basin. We supplemented our simulation outcomes by collecting expert knowledge (from farmers and researchers) regarding observed climate change impacts on temperate orchards as well as future risks and concerns generated by climate change. Results showed that northern African growing regions have experienced major chill losses, a likely cause of the irregular and delayed bloom highlighted by experts. The same regions, together with southern Europe, may lose up to 30 Chill Portions by 2050 under a moderate warming scenario. For the future, experts foresee increasing risk of spring frost in early-blooming cultivars, exacerbated bloom-related problems and increasing occurrence of heat waves. Our results provide evidence of likely climate change impacts on temperate orchards. Expert knowledge proved instrumental in interpreting the simulation results as well as in orienting climate change adaptation strategies. The results we present are useful for farmers and orchard managers planning new plantings, as well as for researchers and policy makers developing strategies to adapt fruit orchards to the impacts of climate change.

Investing in nature-based solutions: Cost profiles of collective-action watershed investment programs - Shiteng Kang; Timm Kroeger; Daniel Shemie; Marta Echavarria; Tamara Montalvo; Leah L. Bremer; Genevieve Bennett; Samuel Roiphe Barreto; Henrique Bracale; Claudia Calero; Aldo Cardenas; Julián Cardona; et al. (Ecosystem Services, 2023)

Quantifying elevational effect on the geometric body shape of Russian beetle Carabus exaratus (Coleoptera: Carabidae) - Hugo A. Benítez; Raisa A. Sukhodolskaya; Tamara A. Avtaeva; Scott Escobar-Suárez; Rodrigo Órdenes-Claveria; David Laroze; Raquel Hernández-P; Dmitriy N. Vavilov (Zoologischer Anzeiger, 2023)

A taphonomic analysis of PTK (Bed I, Olduvai Gorge) and its bearing on the interpretation of the dietary and eco-spatial behaviors of early humans - Elia Organista; Abel Moclán; Julia Aramendi; Lucía Cobo-Sánchez; Charles P. Egeland; David Uribelarrea; David Martín-Perea; Marina Vegara-Riquelme; Lucía Hernández-Vivanco; Agness Gidna; Audax Mabula; Enrique Baquedano; et al. (Quaternary Science Reviews, 2023)

New records of continental vertebrates from the Triassic of the Atacama Desert, northern Chile - Rodrigo A. Otero; David Rubilar-Rogers; Sergio Soto-Acuña; Alexander Vargas M.; Gonzalo Mella Rojas; Raúl Ugalde; Osvaldo Rojas; Jennyfer Rojas; Fernando E. Novas (Journal of South American Earth Sciences, 2023)

Correction to: Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Facing the palimpsest conundrum: an archaeo-stratigraphic approach to the intra-site analysis of SHK Extension (Bed II, Olduvai Gorge, Tanzania) - Cristina Fraile-Márquez; Fernando Diez-Martín; Javier Duque-Martínez; David Uribelarrea; Policarpo Sánchez-Yustos; Sara de Francisco; Enrique Baquedano; Audax Mabulla; Manuel Domínguez-Rodrigo (Archaeological and Anthropological Sciences, 2022)

Effects of Tidal Stream Energy Exploitation on Estuarine Circulation and Its Seasonal Variability - Marcos Sánchez; David Mateo Fouz; Iván López; Rodrigo Carballo; Gregorio Iglesias (Journal of Marine Science and Engineering, 2022)
Residual flows are of major importance in coastal areas, driving environmental processes such as sediment transport or nutrient dispersion. Consequently, in those areas where a large tidal stream energy resource is available, prior to the installation of a tidal farm, it is imperative to assess how energy extraction affects the residual flows and, in particular, upwelling events. In this paper, the potential effects of different configurations of tidal stream farms on the residual circulation and its seasonality are analysed by means of a case study: Ria de Ortigueira, the westernmost of the Galician Rias Altas (NW Spain). For this purpose, a 3D numerical model was implemented and validated against field measurements. Next, a total of eight case studies, including the operation of bottom-fixed and floating converters under typical summer and winter scenarios, considering upwelling favourable winds, were studied. Overall, when a tidal farm operates, regardless of its configuration and the forcings considered, the resulting general residual flow pattern does not experience significant modifications. This pattern is characterized by a 2D circulation in the inner ria and a positive estuarine circulation in the middle and outer ria. The largest modifications of the residual flow are apparent in the vicinities of the plant, with maximum values of about 0.05 ms−1. Outside this area, the alteration is lower than 0.01 ms−1 and virtually negligible at some distance from the farm where upwelling events develop.

The Dorothy Garrod Site: a new Middle Stone Age locality in Olduvai Gorge, Tanzania - José Manuel Maíllo-Fernández; Juan Marín; David Manuel Martín-Perea; David Uribelarrea; Irene Solano-Megías; Raquel Asiaín; Enrique Baquedano; Manuel Domínguez-Rodrigo; Agness Gidna; Alicia Medialdea; Hekima Mwamakimbula Steven; Daniel Haruni Chilonzi; et al. (Archaeological and Anthropological Sciences, 2022)
Olduvai Gorge (Tanzania) is a key site for the study of human evolution as well as the origin of modern humans and the Middle Stone Age (MSA). In this study, we present a new MSA location named Dorothy Garrod Site (DGS), found in the main branch of Olduvai Gorge. The site has only one archaeological level, located stratigraphically in the Upper Ndutu. Although it has not yet been possible to radiometrically date it, it has yielded numerous archaeological remains with a functional association between the faunal remains and the lithic industry. The fauna identified includes Alcelaphini, Hippotragini, and Equidae, some of which present percussion marks and evidence of burning. The lithic industry involved knapping using discoid methods. The retouched blanks are denticulates and retouched flakes with, up to now, a total absence of points. DGS is therefore a new site that will aid our understanding of modern human occupations in northern Tanzania in a period for which there is a dearth of properly contextualised archaeological evidence.

Tallo: A global tree allometry and crown architecture database - Tommaso Jucker; Fabian Jörg Fischer; Jérôme Chave; David A. Coomes; John Caspersen; Arshad Ali; Grace Jopaul Loubota Panzou; Ted R. Feldpausch; Daniel Falster; Vladimir A. Usoltsev; Stephen Adu‐Bredu; Luciana F. Alves; et al. (Global Change Biology, 2022)
Data capturing multiple axes of tree size and shape, such as a tree's stem diameter, height and crown size, underpin a wide range of ecological research—from developing and testing theory on forest structure and dynamics, to estimating forest carbon stocks and their uncertainties, and integrating remote sensing imagery into forest monitoring programmes. However, these data can be surprisingly hard to come by, particularly for certain regions of the world and for specific taxonomic groups, posing a real barrier to progress in these fields. To overcome this challenge, we developed the Tallo database, a collection of 498,838 georeferenced and taxonomically standardized records of individual trees for which stem diameter, height and/or crown radius have been measured. These data were collected at 61,856 globally distributed sites, spanning all major forested and non‐forested biomes. The majority of trees in the database are identified to species (88%), and collectively Tallo includes data for 5163 species distributed across 1453 genera and 187 plant families. The database is publicly archived under a CC‐BY 4.0 licence and can be access from: https://doi.org/10.5281/zenodo.6637599 . To demonstrate its value, here we present three case studies that highlight how the Tallo database can be used to address a range of theoretical and applied questions in ecology—from testing the predictions of metabolic scaling theory, to exploring the limits of tree allometric plasticity along environmental gradients and modelling global variation in maximum attainable tree height. In doing so, we provide a key resource for field ecologists, remote sensing researchers and the modelling community working together to better understand the role that trees play in regulating the terrestrial carbon cycle.

AMAZONIA CAMTRAP: A data set of mammal, bird, and reptile species recorded with camera traps in the Amazon forest - Ana Carolina Antunes; Anelise Montanarin; Diogo Maia Gräbin; Erison Carlos dos Santos Monteiro; Fernando Ferreira de Pinho; Guilherme Costa Alvarenga; Jorge Ahumada; Robert B. Wallace; Emiliano Esterci Ramalho; Adrian Paul Ashton Barnett; Alex Bager; Alexandre Martins Costa Lopes; et al. (Ecology, 2022)
The Amazon forest has the highest biodiversity on Earth. However, information on Amazonian vertebrate diversity is still deficient and scattered across the published, peer‐reviewed, and gray literature and in unpublished raw data. Camera traps are an effective non‐invasive method of surveying vertebrates, applicable to different scales of time and space. In this study, we organized and standardized camera trap records from different Amazon regions to compile the most extensive data set of inventories of mammal, bird, and reptile species ever assembled for the area. The complete data set comprises 154,123 records of 317 species (185 birds, 119 mammals, and 13 reptiles) gathered from surveys from the Amazonian portion of eight countries (Brazil, Bolivia, Colombia, Ecuador, French Guiana, Peru, Suriname, and Venezuela). The most frequently recorded species per taxa were: mammals: Cuniculus paca (11,907 records); birds: Pauxi tuberosa (3713 records); and reptiles: Tupinambis teguixin (716 records). The information detailed in this data paper opens up opportunities for new ecological studies at different spatial and temporal scales, allowing for a more accurate evaluation of the effects of habitat loss, fragmentation, climate change, and other human‐mediated defaunation processes in one of the most important and threatened tropical environments in the world. The data set is not copyright restricted; please cite this data paper when using its data in publications and we also request that researchers and educators inform us of how they are using these data.

Phytopythium chamaehyphon causing corm and root rot of uncultivated taro (Colocasia esculenta) - David Galo; Cesar Escalante; Rodrigo Diaz; John E. Hartgerink; Rodrigo A. Valverde (European Journal of Plant Pathology, 2022)

Preliminary Research: Application of Non-Invasive Measure of Cytochrome c Oxidase Redox States and Mitochondrial Function in a Porcine Model of Carbon Monoxide Poisoning - Alistair Lewis; Rodrigo M. Forti; Oladunni Alomaja; Clementina Mesaros; Sarah Piel; John C. Greenwood; Fatima M. Talebi; Constantine D. Mavroudis; Matthew Kelly; Shih-Han Kao; Frances S. Shofer; Johannes K. Ehinger; et al. (Journal of Medical Toxicology, 2022)

Framework for Improving Land Boundary Conditions in Ocean Regional Products - Francisco Campuzano; Flávio Santos; Lucian Simionesei; Ana R. Oliveira; Estrella Olmedo; Antonio Turiel; Rodrigo Fernandes; David Brito; Marco Alba; Antonio Novellino; Ramiro Neves (Journal of Marine Science and Engineering, 2022)
The coupling of coastal or regional ocean models to hydrological models or observed data is currently an uncommon practice in operational oceanography. Though hydrological models are regarded as a powerful and useful tool for estimating the quantity and quality of freshwater running in a watershed, they fail to provide accurate results for river flow reaching the coastal area due to water-management activities occurring within the river catchment, activities such as human consumption, irrigation, storage, etc. For this reason, many coastal and regional ocean models continue to impose surface zero-salinity discharges as land boundary conditions for representing such a dynamic boundary. Moreover, river flows are based in climatologies, thus neglecting seasonal and interannual variability. To achieve those objectives, this study proposes an integrated methodology ranging from watershed models to validation in the coastal area and passing through methods and proxies for integrating the freshwater flows into regional ocean models. The main objective of this study is to explore the results obtained by using more sophisticated land boundary conditions based on the capacities of state-of-the-art hydrologic models combined with observation networks. In addition to the evaluation of the source of river-flow data, this work also explores the use of estuarine proxies based on simple modelling grids. The estuarine proxies enable the incorporation of the mixing processes that take place in estuaries into the land fluxes and obtain the plume momentum. The watershed, estuarine proxies, and ocean were modelled using the MOHID Water modelling system and evaluated in western Iberia waters. The modelling results served to illustrate the sea surface salinity extension of the Western Iberia Buoyant Plume (WIBP) during an extreme event in March 2018.

Pyrolysis of Coconut Inflorescence Wastes: Production, Effects of Parameters, Characterization and Optimization of Phenolic-Rich Bio-Oil - Rodrigo Oliveira Farias; Pollyanna Vanessa Santos Lins; Rafaela Gabriel; Alson David Rodrigues Silva; Lívia Luísa Melo Carvalho; Lucas Meili; Allan Almeida Albuquerque; Sandra Helena Vieira Carvalho; João Inácio Soletti; Mozart Daltro Bispo (International Journal of Environmental Research, 2022)

Acetylcholinesterase inhibitory activity of Ocotea pomaderroides extracts: HPLC-MS/MS characterization and molecular modeling studies - Isabella M. A. Reis; Dayse S. A. Cassiano; Rodrigo S. Conceição; Humberto F. de Freitas; Samuel S. da R. Pita; Jorge M. David; Alexsandro Branco (Natural Product Research, 2022)

Severity of SARS-CoV-2 infection is linked to double-negative (CD27− IgD−) B cell subset numbers - Rodrigo Cervantes-Díaz; Víctor Andrés Sosa-Hernández; Jiram Torres-Ruíz; Sandra Romero-Ramírez; Mariana Cañez-Hernández; Alfredo Pérez-Fragoso; José C. Páez-Franco; David E. Meza-Sánchez; Miriam Pescador-Rojas; Víctor Adrián Sosa-Hernández; Diana Gómez-Martín; José L. Maravillas-Montero (Inflammation Research, 2022)

From anecdotes to quantification: advances in characterizing volcanic eruption impacts on the built environment - Natalia Irma Deligne; Susanna F. Jenkins; Elinor S. Meredith; George T. Williams; Graham S. Leonard; Carol Stewart; Thomas M. Wilson; Sébastien Biass; Daniel M. Blake; Russell J. Blong; Costanza Bonadonna; Rodrigo Calderon B.; et al. (Bulletin of Volcanology, 2022)

Antitumor effect of Cymbopogon densiflorus (Linneu) essential oil in bladder cancer cells - Gizele Lucia da Costa Pereira; Tamires Cunha Almeida; Janaina Brandão Seibert; Tatiane Roquete Amparo; Rodrigo Dian de Oliveira Aguiar Soares; Ivanildes Vasconcelos Rodrigues; Gustavo Henrique Bianco de Souza; Orlando David Henrique dos Santos; Glenda Nicioli da Silva (Natural Product Research, 2021)

Correction to: Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)

Sedimentary stratigraphy of Lake Chalco (Central Mexico) during its formative stages - Rodrigo Martínez-Abarca; Beatriz Ortega-Guerrero; Socorro Lozano-García; Margarita Caballero; Blas Valero-Garcés; David McGee; Erik T. Brown; Mona Stockhecke; Alastair G. E. Hodgetts (International Journal of Earth Sciences, 2021)

A “Dirty” Footprint: Macroinvertebrate diversity in Amazonian Anthropic Soils - Wilian C. Demetrio; Ana C. Conrado; Agno N. S. Acioli; Alexandre C. Ferreira; Marie L. C. Bartz; Samuel W. James; Elodie da Silva; Lilianne S. Maia; Gilvan C. Martins; Rodrigo S. Macedo; David W. G. Stanton; Patrick Lavelle; et al. (Global Change Biology, 2021)
Amazonian rainforests, once thought to be pristine wilderness, are increasingly known to have been widely inhabited, modified, and managed prior to European arrival, by human populations with diverse cultural backgrounds. Amazonian Dark Earths (ADEs) are fertile soils found throughout the Amazon Basin, created by pre‐Columbian societies with sedentary habits. Much is known about the chemistry of these soils, yet their zoology has been neglected. Hence, we characterized soil fertility, macroinvertebrate communities, and their activity at nine archeological sites in three Amazonian regions in ADEs and adjacent reference soils under native forest (young and old) and agricultural systems. We found 673 morphospecies and, despite similar richness in ADEs (385 spp.) and reference soils (399 spp.), we identified a tenacious pre‐Columbian footprint, with 49% of morphospecies found exclusively in ADEs. Termite and total macroinvertebrate abundance were higher in reference soils, while soil fertility and macroinvertebrate activity were higher in the ADEs, and associated with larger earthworm quantities and biomass. We show that ADE habitats have a unique pool of species, but that modern land use of ADEs decreases their populations, diversity, and contributions to soil functioning. These findings support the idea that humans created and sustained high‐fertility ecosystems that persist today, altering biodiversity patterns in Amazonia.

Microbiome and oral squamous cell carcinoma: a possible interplay on iron metabolism and its impact on tumor microenvironment - Rodrigo Alex Arthur; Rafael dos Santos Bezerra; João Paulo Bianchi Ximenez; Bruna Laís Merlin; Raphael de Andrade Morraye; João Valentini Neto; Natália Melo Nasser Fava; David Livingstone Alves Figueiredo; Carlos Alberto Oliveira de Biagi; Maria Jara Montibeller; Jhefferson Barbosa Guimarães; Ellen Gomes Alves; et al. (Brazilian Journal of Microbiology, 2021)

Fifteen days of moderate normobaric hypoxia does not affect mitochondrial function, and related genes and proteins, in healthy men - Alessandra Ferri; Xu Yan; Jujiao Kuang; Cesare Granata; Rodrigo S. F. Oliveira; Christopher P. Hedges; Adriano E. Lima-Silva; Francois Billaut; David J. Bishop (European Journal of Applied Physiology, 2021)

Identifying dominant environmental predictors of freshwater wetland methane fluxes across diurnal to seasonal time scales - Sara H. Knox; Sheel Bansal; Gavin McNicol; Karina Schafer; Cove Sturtevant; Masahito Ueyama; Alex C. Valach; Dennis Baldocchi; Kyle Delwiche; Ankur R. Desai; Eugenie Euskirchen; Jinxun Liu; et al. (Global Change Biology, 2021)
While wetlands are the largest natural source of methane (CH 4 ) to the atmosphere, they represent a large source of uncertainty in the global CH 4 budget due to the complex biogeochemical controls on CH 4 dynamics. Here we present, to our knowledge, the first multi‐site synthesis of how predictors of CH 4 fluxes (FCH4) in freshwater wetlands vary across wetland types at diel, multiday (synoptic), and seasonal time scales. We used several statistical approaches (correlation analysis, generalized additive modeling, mutual information, and random forests) in a wavelet‐based multi‐resolution framework to assess the importance of environmental predictors, nonlinearities and lags on FCH4 across 23 eddy covariance sites. Seasonally, soil and air temperature were dominant predictors of FCH4 at sites with smaller seasonal variation in water table depth (WTD). In contrast, WTD was the dominant predictor for wetlands with smaller variations in temperature (e.g., seasonal tropical/subtropical wetlands). Changes in seasonal FCH4 lagged fluctuations in WTD by ~17 ± 11 days, and lagged air and soil temperature by median values of 8 ± 16 and 5 ± 15 days, respectively. Temperature and WTD were also dominant predictors at the multiday scale. Atmospheric pressure (PA) was another important multiday scale predictor for peat‐dominated sites, with drops in PA coinciding with synchronous releases of CH 4 . At the diel scale, synchronous relationships with latent heat flux and vapor pressure deficit suggest that physical processes controlling evaporation and boundary layer mixing exert similar controls on CH 4 volatilization, and suggest the influence of pressurized ventilation in aerenchymatous vegetation. In addition, 1‐ to 4‐h lagged relationships with ecosystem photosynthesis indicate recent carbon substrates, such as root exudates, may also control FCH4. By addressing issues of scale, asynchrony, and nonlinearity, this work improves understanding of the predictors and timing of wetland FCH4 that can inform future studies and models, and help constrain wetland CH 4 emissions.

Reproducibility and accuracy of microscale thermophoresis in the NanoTemper Monolith: a multi laboratory benchmark study - Blanca López-Méndez; Bruno Baron; Chad A. Brautigam; Thomas A. Jowitt; Stefan H. Knauer; Stephan Uebel; Mark A. Williams; Arthur Sedivy; Olga Abian; Celeste Abreu; Malgorzata Adamczyk; Wojciech Bal; et al. (European Biophysics Journal, 2021)
Microscale thermophoresis (MST), and the closely related Temperature Related Intensity Change (TRIC), are synonyms for a recently developed measurement technique in the field of biophysics to quantify biomolecular interactions, using the (capillary-based) NanoTemper Monolith and (multiwell plate-based) Dianthus instruments. Although this technique has been extensively used within the scientific community due to its low sample consumption, ease of use, and ubiquitous applicability, MST/TRIC has not enjoyed the unambiguous acceptance from biophysicists afforded to other biophysical techniques like isothermal titration calorimetry (ITC) or surface plasmon resonance (SPR). This might be attributed to several facts, e.g., that various (not fully understood) effects are contributing to the signal, that the technique is licensed to only a single instrument developer, NanoTemper Technology, and that its reliability and reproducibility have never been tested independently and systematically. Thus, a working group of ARBRE-MOBIEU has set up a benchmark study on MST/TRIC to assess this technique as a method to characterize biomolecular interactions. Here we present the results of this study involving 32 scientific groups within Europe and two groups from the US, carrying out experiments on 40 Monolith instruments , employing a standard operation procedure and centrally prepared samples. A protein–small molecule interaction, a newly developed protein–protein interaction system and a pure dye were used as test systems. We characterized the instrument properties and evaluated instrument performance, reproducibility, the effect of different analysis tools, the influence of the experimenter during data analysis, and thus the overall reliability of this method.

Quantifying 25 years of disease‐caused declines in Tasmanian devil populations: host density drives spatial pathogen spread - Calum X. Cunningham; Sebastien Comte; Hamish McCallum; David G. Hamilton; Rodrigo Hamede; Andrew Storfer; Tracey Hollings; Manuel Ruiz‐Aravena; Douglas H. Kerlin; Barry W. Brook; Greg Hocking; Manna E. Jones (Ecology Letters, 2021)
Infectious diseases are strong drivers of wildlife population dynamics, however, empirical analyses from the early stages of pathogen emergence are rare. Tasmanian devil facial tumour disease (DFTD), discovered in 1996, provides the opportunity to study an epizootic from its inception. We use a pattern‐oriented diffusion simulation to model the spatial spread of DFTD across the species' range and quantify population effects by jointly modelling multiple streams of data spanning 35 years. We estimate the wild devil population peaked at 53 000 in 1996, less than half of previous estimates. DFTD spread rapidly through high‐density areas, with spread velocity slowing in areas of low host densities. By 2020, DFTD occupied >90% of the species' range, causing 82% declines in local densities and reducing the total population to 16 900. Encouragingly, our model forecasts the population decline should level‐off within the next decade, supporting conservation management focused on facilitating evolution of resistance and tolerance.

Water scarcity in central Chile: the effect of climate and land cover changes on hydrologic resources - Ignacio Fuentes; Rodrigo Fuster; David Avilés; Willem Vervoort (Hydrological Sciences Journal, 2021)

Effects of stocking density on survival, growth and stress resistance of juvenile tambaqui (Colossoma macropomum) reared in a recirculating aquaculture system (RAS) - Walisson de Souza e Silva; Andre Lima Ferreira; Luanna do Carmo Neves; Nathália Soares Ferreira; Glauber David Almeida Palheta; Rodrigo Takata; Ronald Kennedy Luz (Aquaculture International, 2021)

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

Top-down characterization of resource use in LCA: from problem definition of resource use to operational characterization factors for dissipation of elements to the environment - Lauran van Oers; Jeroen B. Guinée; Reinout Heijungs; Rita Schulze; Rodrigo A. F. Alvarenga; Jo Dewulf; Johannes Drielsma; David Sanjuan-Delmás; Tobias C. Kampmann; Glenn Bark; Ainara Garcia Uriarte; Pierre Menger; et al. (The International Journal of Life Cycle Assessment, 2020)
Purpose The methods for assessing the impact of using abiotic resources in life cycle assessment (LCA) have always been heavily debated. One of the main reasons for this is the lack of a common understanding of the problem related to resource use. This article reports the results of an effort to reach such common understanding between different stakeholder groups and the LCA community. For this, a top-down approach was applied. Methods To guide the process, a four-level top-down framework was used to (1) demarcate the problem that needs to be assessed, (2) translate this into a modeling concept, (3) derive mathematical equations and fill these with data necessary to calculate the characterization factors, and (4) align the system boundaries and assumptions that are made in the life cycle impact assessment (LCIA) model and the life cycle inventory (LCI) model. Results We started from the following definition of the problem of using resources: the decrease of accessibility on a global level of primary and/or secondary elements over the very long term or short term due to the net result of compromising actions. The system model distinguishes accessible and inaccessible stocks in both the environment and the technosphere. Human actions can compromise the accessible stock through environmental dissipation, technosphere hibernation, and occupation in use or through exploration. As a basis for impact assessment , we propose two parameters: the global change in accessible stock as a net result of the compromising actions and the global amount of the accessible stock. We propose three impact categories for the use of elements: environmental dissipation, technosphere hibernation, and occupation in use, with associated characterization equations for two different time horizons. Finally, preliminary characterization factors are derived and applied in a simple illustrative case study for environmental dissipation. Conclusions Due to data constraints, at this moment, only characterization factors for “dissipation to the environment” over a very-long-term time horizon could be elaborated. The case study shows that the calculation of impact scores might be hampered by insufficient LCI data. Most presently available LCI databases are far from complete in registering the flows necessary to assess the impacts on the accessibility of elements. While applying the framework, various choices are made that could plausibly be made differently. We invite our peers to also use this top-down framework when challenging our choices and elaborate that into a consistent set of choices and assumptions when developing LCIA methods.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

First record of the mating behaviour of the spotted surubim Pseudoplatystoma corruscans in the Uruguay River - Lucas A. Pachla; Paula B. Hartmann; Marthoni V. Massaro; Rodrigo Bastian; Fernando M. Pelicice; David A. Reynalte‐Tataje (Journal of Fish Biology, 2020)
The spotted surubim Pseudoplatystoma corruscans is a large migratory catfish native to the La Plata and San Francisco basins. Nonetheless, its reproductive dynamics and behaviour remain poorly understood. This brief note provides the first record of the mating behaviour of P. corruscans in natural conditions. This behaviour was observed in the main channel of the Middle Uruguay River (Brazil). A school of approximately 25 fish, 5 females (with protruding abdomen and larger body size) and 20 males, were followed and videotaped. The largest female led the school, followed by other fish. Some males disputed repeatedly the posterior region of the females, whereas other males continuously repelled them. Eventually, some males, apparently exhausted, floated belly up. During this event, males were in a state of pronounced agitation, and some had abrasions in the head. Polygamy characterized the mating behaviour of P. corruscans .

High-throughput microRNA profile in adult and pediatric primary glioblastomas: the role of miR-10b-5p and miR-630 in the tumor aggressiveness - Luiz Guilherme Darrigo Junior; Mirella Baroni; Régia Caroline Peixoto Lira; Silvia Teixeira; Paola Fernanda Fedatto; Vanessa Silva Silveira; Veridiana Kill Suazo; Luciana Chain Veronez; Rodrigo Alexandre Panepucci; David Santos Marco Antônio; José Andres Yunes; Silvia Regina Brandalise; et al. (Molecular Biology Reports, 2020)

5 km front crawl in pool and open water swimming: breath-by-breath energy expenditure and kinematic analysis - Rodrigo Zacca; Vânia Neves; Tiago da Silva Oliveira; Susana Soares; Luís Manuel Pinto Lopes Rama; Flávio Antônio de Souza Castro; João Paulo Vilas-Boas; David B. Pyne; Ricardo J. Fernandes (European Journal of Applied Physiology, 2020)

How to create an operational multi-model of seasonal forecasts? - Stephan Hemri; Jonas Bhend; Mark A. Liniger; Rodrigo Manzanas; Stefan Siegert; David B. Stephenson; José M. Gutiérrez; Anca Brookshaw; Francisco J. Doblas-Reyes (Climate Dynamics, 2020)
Seasonal forecasts of variables like near-surface temperature or precipitation are becoming increasingly important for a wide range of stakeholders. Due to the many possibilities of recalibrating, combining, and verifying ensemble forecasts, there are ambiguities of which methods are most suitable. To address this we compare approaches how to process and verify multi-model seasonal forecasts based on a scientific assessment performed within the framework of the EU Copernicus Climate Change Service (C3S) Quality Assurance for Multi-model Seasonal Forecast Products (QA4Seas) contract C3S 51 lot 3. Our results underpin the importance of processing raw ensemble forecasts differently depending on the final forecast product needed. While ensemble forecasts benefit a lot from bias correction using climate conserving recalibration, this is not the case for the intrinsically bias adjusted multi-category probability forecasts. The same applies for multi-model combination. In this paper, we apply simple, but effective, approaches for multi-model combination of both forecast formats. Further, based on existing literature we recommend to use proper scoring rules like a sample version of the continuous ranked probability score and the ranked probability score for the verification of ensemble forecasts and multi-category probability forecasts, respectively. For a detailed global visualization of calibration as well as bias and dispersion errors, using the Chi-square decomposition of rank histograms proved to be appropriate for the analysis performed within QA4Seas.

Comparative landscape genetics reveals differential effects of environment on host and pathogen genetic structure in Tasmanian devils ( Sarcophilus harrisii ) and their transmissible tumour - Christopher P. Kozakiewicz; Lauren Ricci; Austin H. Patton; Amanda R. Stahlke; Sarah A. Hendricks; Mark J. Margres; Manuel Ruiz‐Aravena; David G. Hamilton; Rodrigo Hamede; Hamish McCallum; Menna E. Jones; Paul A. Hohenlohe; et al. (Molecular Ecology, 2020)
Genetic structure in host species is often used to predict disease spread. However, host and pathogen genetic variation may be incongruent. Understanding landscape factors that have either concordant or divergent influence on host and pathogen genetic structure is crucial for wildlife disease management. Devil facial tumour disease (DFTD) was first observed in 1996 and has spread throughout almost the entire Tasmanian devil geographic range, causing dramatic population declines. Whereas DFTD is predominantly spread via biting among adults, devils typically disperse as juveniles, which experience low DFTD prevalence. Thus, we predicted little association between devil and tumour population structure and that environmental factors influencing gene flow differ between devils and tumours. We employed a comparative landscape genetics framework to test the influence of environmental factors on patterns of isolation by resistance (IBR) and isolation by environment (IBE) in devils and DFTD. Although we found evidence for broad‐scale costructuring between devils and tumours, we found no relationship between host and tumour individual genetic distances. Further, the factors driving the spatial distribution of genetic variation differed for each. Devils exhibited a strong IBR pattern driven by major roads, with no evidence of IBE. By contrast, tumours showed little evidence for IBR and a weak IBE pattern with respect to elevation in one of two tumour clusters we identify herein. Our results warrant caution when inferring pathogen spread using host population genetic structure and suggest that reliance on environmental barriers to host connectivity may be ineffective for managing the spread of wildlife diseases. Our findings demonstrate the utility of comparative landscape genetics for identifying differential factors driving host dispersal and pathogen transmission.

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Changing Biogeochemistry of the Southern Ocean and Its Ecosystem Implications - Sian F. Henley; Emma L. Cavan; Sarah E. Fawcett; Rodrigo Kerr; Thiago Monteiro; Robert M. Sherrell; Andrew R. Bowie; Philip W. Boyd; David K. A. Barnes; Irene R. Schloss; Tanya Marshall; Raquel Flynn; et al. (Frontiers in Marine Science, 2020)

Experimental approaches to the development of use-wear traces on volcanic rocks: basalts - Patricia Bello-Alonso; Joseba Rios-Garaizar; Joaquín Panera; David Manuel Martín-Perea; Susana Rubio-Jara; Alfredo Pérez-González; Raquel Rojas-Mendoza; Manuel Domínguez-Rodrigo; Enrique Baquedano; Manuel Santonja (Archaeological and Anthropological Sciences, 2020)

Improved soybean transformation for efficient and high throughput transgenic production - Dayakar Pareddy; Siva Chennareddy; Geny Anthony; Nagesh Sardesai; Tejinder Mall; Tatyana Minnicks; Olga Karpova; Lauren Clark; David Griffin; Brandon Bishop; Nolan Shumway; Pon Samuel; et al. (Transgenic Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Global agricultural productivity is threatened by increasing pollinator dependence without a parallel increase in crop diversification - Marcelo A. Aizen; Sebastián Aguiar; Jacobus C. Biesmeijer; Lucas A. Garibaldi; David W. Inouye; Chuleui Jung; Dino J. Martins; Rodrigo Medel; Carolina L. Morales; Hien Ngo; Anton Pauw; Robert J. Paxton; et al. (Global Change Biology, 2019)
The global increase in the proportion of land cultivated with pollinator‐dependent crops implies increased reliance on pollination services. Yet agricultural practices themselves can profoundly affect pollinator supply and pollination. Extensive monocultures are associated with a limited pollinator supply and reduced pollination, whereas agricultural diversification can enhance both. Therefore, areas where agricultural diversity has increased, or at least been maintained, may better sustain high and more stable productivity of pollinator‐dependent crops. Given that >80% of all crops depend, to varying extents, on insect pollination, a global increase in agricultural pollinator dependence over recent decades might have led to a concomitant increase in agricultural diversification. We evaluated whether an increase in the area of pollinator‐dependent crops has indeed been associated with an increase in agricultural diversity, measured here as crop diversity, at the global, regional, and country scales for the period 1961–2016. Globally, results show a relatively weak and decelerating rise in agricultural diversity over time that was largely decoupled from the strong and continually increasing trend in agricultural dependency on pollinators. At regional and country levels, there was no consistent relationship between temporal changes in pollinator dependence and crop diversification. Instead, our results show heterogeneous responses in which increasing pollinator dependence for some countries and regions has been associated with either an increase or a decrease in agricultural diversity. Particularly worrisome is a rapid expansion of pollinator‐dependent oilseed crops in several countries of the Americas and Asia that has resulted in a decrease in agricultural diversity. In these regions, reliance on pollinators is increasing, yet agricultural practices that undermine pollination services are expanding. Our analysis has thereby identified world regions of particular concern where environmentally damaging practices associated with large‐scale, industrial agriculture threaten key ecosystem services that underlie productivity, in addition to other benefits provided by biodiversity.

Extreme Marine Heatwaves Alter Kelp Forest Community Near Its Equatorward Distribution Limit - Nur Arafeh-Dalmau; Gabriela Montaño-Moctezuma; José A. Martínez; Rodrigo Beas-Luna; David S. Schoeman; Guillermo Torres-Moye (Frontiers in Marine Science, 2019)

Ranking of Placer Gold Prospects in Chile Through Analytic Hierarchy Process - J. Joaquín Jara; Francisco Moreno; Raúl Jara; Francisco Dubournais; Rodrigo Mata; David Peters; Carlos Marquardt; Gustavo Lagos (Natural Resources Research, 2019)

Genome sequencing of Burkholderia contaminans LTEB11 reveals a lipolytic arsenal of biotechnological interest - Robson Carlos Alnoch; Rodrigo Luis Alves Cardoso; Dieval Guizelini; Eduardo Balsanelli; Michelle Zibetti Tadra-Sfeir; Fábio de Oliveira Pedrosa; Guilherme Lanzi Sassaki; Leonardo Magalhães Cruz; David Alexander Mitchell; Emanuel Maltempi de Souza; Nadia Krieger; Marcelo Muller-Santos (Brazilian Journal of Microbiology, 2019)

Scaling issues of neutral theory reveal violations of ecological equivalence for dominant Amazonian tree species - Edwin Pos; Juan Ernesto Guevara; Jean‐François Molino; Daniel Sabatier; Olaf S. Bánki; Nigel C.A. Pitman; Hugo F. Mogollón; Roosevelt García‐Villacorta; David Neill; Oliver L. Phillips; Carlos Cerón; Marcos Ríos Paredes; et al. (Ecology Letters, 2019)
Neutral models are often used as null models, testing the relative importance of niche versus neutral processes in shaping diversity. Most versions, however, focus only on regional scale predictions and neglect local level contributions. Recently, a new formulation of spatial neutral theory was published showing an incompatibility between regional and local scale fits where especially the number of rare species was dramatically under‐predicted. Using a forward in time semi‐spatially explicit neutral model and a unique large‐scale Amazonian tree inventory data set, we show that neutral theory not only underestimates the number of rare species but also fails in predicting the excessive dominance of species on both regional and local levels. We show that although there are clear relationships between species composition, spatial and environmental distances, there is also a clear differentiation between species able to attain dominance with and without restriction to specific habitats. We conclude therefore that the apparent dominance of these species is real, and that their excessive abundance can be attributed to fitness differences in different ways, a clear violation of the ecological equivalence assumption of neutral theory.

Incentives for aquaculture in protected areas: possible consequences for biodiversity and its services in southern Brazil - Jorge L. Rodrigues Filho; Débora Lugli-Bernardes; Lia Mayrink Sabinson; Rodrigo Machado; Harry Boos; Luciano Lorenzi; Marcelo Manoel Domingos; David Valença Dantas (Biodiversity and Conservation, 2019)

Ingestion of plastic fragments by the Guri sea catfish Genidens genidens (Cuvier, 1829) in a subtropical coastal estuarine system - David V. Dantas; Cristian I. R. Ribeiro; Catarina de C. A. Frischknecht; Rodrigo Machado; Eduardo G. G. Farias (Environmental Science and Pollution Research, 2019)

Plant core DNA barcode performance at a local scale: identification of the conifers of the state of Hidalgo, Mexico - Sergio Hernández-León; Damon P. Little; Otilio Acevedo-Sandoval; David S. Gernandt; Rodrigo Rodríguez-Laguna; Mariana Saucedo-García; Oscar Arce-Cervantes; Ramón Razo-Zárate; Josefa Espitia-López (Systematics and Biodiversity, 2018)

Fluvial spatial taphonomy: a new method for the study of post-depositional processes - Manuel Domínguez-Rodrigo; Lucía Cobo-Sánchez; José Yravedra; David Uribelarrea; Carmen Arriaza; Elia Organista; Enrique Baquedano (Archaeological and Anthropological Sciences, 2018)

Does intra-individual neurocognitive variability relate to neuroinvasive disease and quality of life in West Nile Virus? - David P. Sheppard; Steven Paul Woods; Rodrigo Hasbun; Lucrecia Salazar; Melissa S. Nolan; Kristy O. Murray (Journal of NeuroVirology, 2018)

IL-33 signalling in liver immune cells enhances drug-induced liver injury and inflammation - Maísa Mota Antunes; Alan Moreira Araújo; Ariane Barros Diniz; Rafaela Vaz Sousa Pereira; Débora Moreira Alvarenga; Bruna Araújo David; Renata Monti Rocha; Maria Alice Freitas Lopes; Sarah Cozzer Marchesi; Brenda Naemi Nakagaki; Érika Carvalho; Pedro Elias Marques; et al. (Inflammation Research, 2018)

CO 2 exchange and evapotranspiration across dryland ecosystems of southwestern North America - Joel A. Biederman; Russell L. Scott; Tom W. Bell; David R. Bowling; Sabina Dore; Jaime Garatuza‐Payan; Thomas E. Kolb; Praveena Krishnan; Dan J. Krofcheck; Marcy E. Litvak; Gregory E. Maurer; Tilden P. Meyers; et al. (Global Change Biology, 2017)
Global‐scale studies suggest that dryland ecosystems dominate an increasing trend in the magnitude and interannual variability of the land CO 2 sink. However, such analyses are poorly constrained by measured CO 2 exchange in drylands. Here we address this observation gap with eddy covariance data from 25 sites in the water‐limited Southwest region of North America with observed ranges in annual precipitation of 100–1000 mm, annual temperatures of 2–25°C, and records of 3–10 years (150 site‐years in total). Annual fluxes were integrated using site‐specific ecohydrologic years to group precipitation with resulting ecosystem exchanges. We found a wide range of carbon sink/source function, with mean annual net ecosystem production ( NEP ) varying from ‐350 to +330 gC m −2 across sites with diverse vegetation types, contrasting with the more constant sink typically measured in mesic ecosystems. In this region, only forest‐dominated sites were consistent carbon sinks. Interannual variability of NEP , gross ecosystem production ( GEP ), and ecosystem respiration (R eco ) was larger than for mesic regions, and half the sites switched between functioning as C sinks/C sources in wet/dry years. The sites demonstrated coherent responses of GEP and NEP to anomalies in annual evapotranspiration ( ET ), used here as a proxy for annually available water after hydrologic losses. Notably, GEP and R eco were negatively related to temperature, both interannually within site and spatially across sites, in contrast to positive temperature effects commonly reported for mesic ecosystems. Models based on MODIS satellite observations matched the cross‐site spatial pattern in mean annual GEP but consistently underestimated mean annual ET by ~50%. Importantly, the MODIS ‐based models captured only 20–30% of interannual variation magnitude. These results suggest the contribution of this dryland region to variability of regional to global CO 2 exchange may be up to 3–5 times larger than current estimates.

Population genomics applications for conservation: the case of the tropical dry forest dweller Peromyscus melanophrys - Rodrigo Vega; Ella Vázquez-Domínguez; Thomas A. White; David Valenzuela-Galván; Jeremy B. Searle (Conservation Genetics, 2017)

Diadenosine tetraphosphate (Ap4A) inhibits ATP-induced excitotoxicity: a neuroprotective strategy for traumatic spinal cord injury treatment - David Reigada; Rosa María Navarro-Ruiz; Marcos Javier Caballero-López; Ángela Del Águila; Teresa Muñoz-Galdeano; Rodrigo M. Maza; Manuel Nieto-Díaz (Purinergic Signalling, 2017)

Can Andean potatoes be agronomically biofortified with iron and zinc fertilizers? - Peter Kromann; Franklin Valverde; Soraya Alvarado; Rodrigo Vélez; José Pisuña; Byron Potosí; Arturo Taipe; David Caballero; Amalia Cabezas; André Devaux (Plant and Soil, 2017)

Coupling watersheds, estuaries and regional ocean through numerical modelling for Western Iberia: a novel methodology - Francisco Campuzano; David Brito; Manuela Juliano; Rodrigo Fernandes; Hilda de Pablo; Ramiro Neves (Ocean Dynamics, 2016)

Did Homo erectus kill a Pelorovis herd at BK (Olduvai Gorge)? A taphonomic study of BK5 - Elia Organista; Manuel Domínguez-Rodrigo; Charles P. Egeland; David Uribelarrea; Audax Mabulla; Enrique Baquedano (Archaeological and Anthropological Sciences, 2016)

Identification of Dominant Excitation Patterns and Sources of Atrial Fibrillation by Causality Analysis - Miguel Rodrigo; Andreu M. Climent; Alejandro Liberos; David Calvo; Francisco Fernández-Avilés; Omer Berenfeld; Felipe Atienza; Maria S. Guillem (Annals of Biomedical Engineering, 2016)

Erratum to: Vegfr3-CreER T2 mouse, a new genetic tool for targeting the lymphatic system - Ines Martinez-Corral; Lukas Stanczuk; Maike Frye; Maria Helena Ulvmar; Rodrigo Diéguez-Hurtado; David Olmeda; Taija Makinen; Sagrario Ortega (Angiogenesis, 2016)

Vegfr3-CreER T2 mouse, a new genetic tool for targeting the lymphatic system - Ines Martinez-Corral; Lukas Stanczuk; Maike Frye; Maria Helena Ulvmar; Rodrigo Diéguez-Hurtado; David Olmeda; Taija Makinen; Sagrario Ortega (Angiogenesis, 2016)

Thioridazine inhibits gene expression control of the cell wall signaling pathway (CWI) in the human pathogenic fungus Paracoccidioides brasiliensis - Daniela Leite Jabes; Ana Claudia de Freitas Oliveira; Valquíria Campos Alencar; Fabiano Bezerra Menegidio; Débora Liliane Souza Reno; Daiene Souza Santos; David Aciole Barbosa; Renata Ozelami Vilas Boas; Rodrigo Luiz de Oliveira Rodrigues Cunha; Tiago Rodrigues; Regina Costa de Oliveira; Luiz R. Nunes (Molecular Genetics and Genomics, 2016)

Environmental Enrichment Improves Behavior, Cognition, and Brain Functional Markers in Young Senescence-Accelerated Prone Mice (SAMP8) - Christian Griñan-Ferré; David Pérez-Cáceres; Sofía Martínez Gutiérrez-Zetina; Antoni Camins; Verónica Palomera-Avalos; Daniel Ortuño-Sahagún; M. Teresa Rodrigo; M. Pallàs (Molecular Neurobiology, 2016)

A randomized, placebo-controlled pilot trial of the delta opioid receptor agonist AZD2327 in anxious depression - Erica M. Richards; Daniel C. Mathews; David A. Luckenbaugh; Dawn F. Ionescu; Rodrigo Machado-Vieira; Mark J. Niciu; Wallace C. Duncan; Neal M. Nolan; Jose A. Franco-Chaves; Thomas Hudzik; Carla Maciag; Shuang Li; et al. (Psychopharmacology, 2016)

Mineral nutrition and specific leaf area of plants under contrasting long-term fire frequencies: a case study in a mesic savanna in Australia - Marcelo Claro de Souza; Davi Rodrigo Rossatto; Garry David Cook; Ryosuke Fujinuma; Neal William Menzies; Leonor Patricia Cerdeira Morellato; Gustavo Habermann (Trees, 2016)

D-serine plasma concentration is a potential biomarker of (R,S)-ketamine antidepressant response in subjects with treatment-resistant depression - Ruin Moaddel; David A. Luckenbaugh; Ying Xie; Alma Villaseñor; Nancy E. Brutsche; Rodrigo Machado-Vieira; Anuradha Ramamoorthy; Maria Paz Lorenzo; Antonia Garcia; Michel Bernier; Marc C. Torjman; Coral Barbas; et al. (Psychopharmacology, 2015)

Sex-influence of nicotine and nitric oxide on motor coordination and anxiety-related neurophysiological responses - Rodrigo Muñoz-Castañeda; David Díaz; Carmelo A. Ávila-Zarza; José R. Alonso; Eduardo Weruaga (Psychopharmacology, 2014)

Tadalafil-induced improvement in left ventricular diastolic function in resistant hypertension - Rodrigo C. Santos; Ana Paula C. de Faria; Natália R. Barbaro; Rodrigo Modolo; Silvia E. Ferreira-Melo; José R. Matos-Souza; Otávio R. Coelho; Juan C. Yugar-Toledo; Vanessa Fontana; David Calhoun; Heitor Moreno (European Journal of Clinical Pharmacology, 2014)

Optimism and Challenge for Science‐Based Conservation of Migratory Species in and out of U.S. National Parks - JOEL BERGER; STEVEN L. CAIN; ELLEN CHENG; PETER DRATCH; KEVIN ELLISON; JOHN FRANCIS; HERBERT C. FROST; SCOTT GENDE; CRAIG GROVES; WILLIAM A. KARESH; ELAINE LESLIE; GARY MACHLIS; et al. (Conservation Biology, 2014)
Public agencies sometimes seek outside guidance when capacity to achieve their mission is limited. Through a cooperative agreement and collaborations with the U.S. National Park Service (NPS), we developed recommendations for a conservation program for migratory species. Although NPS manages ∼36 million hectares of land and water in 401 units, there is no centralized program to conserve wild animals reliant on NPS units that also migrate hundreds to thousands of kilometers beyond parks. Migrations are imperiled by habitat destruction, unsustainable harvest, climate change, and other impediments. A successful program to counter these challenges requires public support, national and international outreach, and flourishing migrant populations. We recommended two initial steps. First, in the short term, launch or build on a suite of projects for high‐profile migratory species that can serve as proof to demonstrate the centrality of NPS units to conservation at different scales. Second, over the longer term, build new capacity to conserve migratory species. Capacity building will entail increasing the limited knowledge among park staff about how and where species or populations migrate, conditions that enable migration, and identifying species’ needs and resolving them both within and beyond parks. Building capacity will also require ensuring that park superintendents and staff at all levels support conservation beyond statutory borders. Until additional diverse stakeholders and a broader American public realize what can be lost and do more to protect it and engage more with land management agencies to implement actions that facilitate conservation, long distance migrations are increasingly likely to become phenomena of the past. Optimismo y Retos para la Conservación Científicamente Basada de Especies Migratorias Dentro y Fuera de Parques Nacionales de E.U.A.

Drought Influences the Accuracy of Simulated Ecosystem Fluxes: A Model-Data Meta-analysis for Mediterranean Oak Woodlands - Rodrigo Vargas; Oliver Sonnentag; Gab Abramowitz; Arnaud Carrara; Jing Ming Chen; Philippe Ciais; Alexandra Correia; Trevor F. Keenan; Hideki Kobayashi; Jean-Marc Ourcival; Dario Papale; David Pearson; et al. (Ecosystems, 2013)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Spatial and temporal variation of the ichthyoplankton in a subtropical river in Brazil - David Augusto Reynalte-Tataje; Angelo Antônio Agostinho; Andrea Bialetzki; Samara Hermes-Silva; Rodrigo Fernandes; Evoy Zaniboni-Filho (Environmental Biology of Fishes, 2012)

Terrestrial biosphere models need better representation of vegetation phenology: results from the N orth A merican C arbon P rogram S ite S ynthesis - Andrew D. Richardson; Ryan S. Anderson; M. Altaf Arain; Alan G. Barr; Gil Bohrer; Guangsheng Chen; Jing M. Chen; Philippe Ciais; Kenneth J. Davis; Ankur R. Desai; Michael C. Dietze; Danilo Dragoni; et al. (Global Change Biology, 2012)
Phenology, by controlling the seasonal activity of vegetation on the land surface, plays a fundamental role in regulating photosynthesis and other ecosystem processes, as well as competitive interactions and feedbacks to the climate system. We conducted an analysis to evaluate the representation of phenology, and the associated seasonality of ecosystem‐scale CO 2 exchange, in 14 models participating in the N orth A merican C arbon P rogram S ite S ynthesis. Model predictions were evaluated using long‐term measurements (emphasizing the period 2000–2006) from 10 forested sites within the A meri F lux and F luxnet‐ C anada networks. In deciduous forests, almost all models consistently predicted that the growing season started earlier, and ended later, than was actually observed; biases of 2 weeks or more were typical. For these sites, most models were also unable to explain more than a small fraction of the observed interannual variability in phenological transition dates. Finally, for deciduous forests, misrepresentation of the seasonal cycle resulted in over‐prediction of gross ecosystem photosynthesis by +160 ± 145 g C m −2 yr −1 during the spring transition period and +75 ± 130 g C m −2 yr −1 during the autumn transition period (13% and 8% annual productivity, respectively) compensating for the tendency of most models to under‐predict the magnitude of peak summertime photosynthetic rates. Models did a better job of predicting the seasonality of CO 2 exchange for evergreen forests. These results highlight the need for improved understanding of the environmental controls on vegetation phenology and incorporation of this knowledge into better phenological models. Existing models are unlikely to predict future responses of phenology to climate change accurately and therefore will misrepresent the seasonality and interannual variability of key biosphere–atmosphere feedbacks and interactions in coupled global climate models.

An International Quiet Ocean Experiment - Ian Boyd; George Frisk; Ed Urban; Peter Tyack; Jesse Ausubel; Sophie Seeyave; Doug Cato; Brendon Southall; Michael Weise; Rex Andrew; Tomonari Akamatsu; René Dekeling; et al. (Oceanography, 2011)

Hypocretin 1/orexin A in the ventral tegmental area enhances dopamine responses to cocaine and promotes cocaine self-administration - Rodrigo A. España; James R. Melchior; David C. S. Roberts; Sara R. Jones (Psychopharmacology, 2011)

Isolation and characterization of microsatellite markers in the southern hake, Merluccius australis - Mark A. Renshaw; David S. Portnoy; Rodrigo Vidal; John R. Gold (Conservation Genetics Resources, 2011)

Rapid response of a grassland ecosystem to an experimental manipulation of a keystone rodent and domestic livestock - Ana D. Davidson; Eduardo Ponce; David C. Lightfoot; Ed L. Fredrickson; James H. Brown; Juan Cruzado; Sandra L. Brantley; Rodrigo Sierra-Corona; Rurik List; David Toledo; Gerardo Ceballos (Ecology, 2010)
Megaherbivores and small burrowing mammals commonly coexist and play important functional roles in grassland ecosystems worldwide. The interactive effects of these two functional groups of herbivores in shaping the structure and function of grassland ecosystems are poorly understood. In North America's central grasslands, domestic cattle ( Bos taurus ) have supplanted bison ( Bison bison ), and now coexist with prairie dogs ( Cynomys spp.), a keystone burrowing rodent. Understanding the ecological relationships between cattle and prairie dogs and their independent and interactive effects is essential to understanding the ecology and important conservation issues affecting North American grassland ecosystems. To address these needs, we established a long‐term manipulative experiment that separates the independent and interactive effects of prairie dogs and cattle using a 2 × 2 factorial design. Our study is located in the Janos‐Casas Grandes region of northwestern Chihuahua, Mexico, which supports one of the largest remaining complexes of black‐tailed prairie dogs ( C. ludovicianus ). Two years of posttreatment data show nearly twofold increases in prairie dog abundance on plots grazed by cattle compared to plots without cattle. This positive effect of cattle on prairie dogs resulted in synergistic impacts when they occurred together. Vegetation height was significantly lower on the plots where both species co‐occurred compared to where either or both species was absent. The treatments also significantly affected abundance and composition of other grassland animal species, including grasshoppers and banner‐tailed kangaroo rats ( Dipodomys spectabilis ). Our results demonstrate that two different functional groups of herbivorous mammals, burrowing mammals and domestic cattle, have distinctive and synergistic impacts in shaping the structure and function of grassland ecosystems.

A composite transcriptional signature differentiates responses towards closely related herbicides in Arabidopsis thaliana and Brassica napus - Malay Das; Jay R. Reichman; Georg Haberer; Gerhard Welzl; Felipe F. Aceituno; Michael T. Mader; Lidia S. Watrud; Thomas G. Pfleeger; Rodrigo A. Gutiérrez; Anton R. Schäffner; David M. Olszyk (Plant Molecular Biology, 2010)

Vulnerable island carnivores: the endangered endemic dwarf procyonids from Cozumel Island - Katherine W. McFadden; Denise García-Vasco; Alfredo D. Cuarón; David Valenzuela-Galván; Rodrigo A. Medellín; Matthew E. Gompper (Biodiversity and Conservation, 2010)

Transmission dynamics of Tasmanian devil facial tumor disease may lead to disease‐induced extinction - Hamish McCallum; Menna Jones; Clare Hawkins; Rodrigo Hamede; Shelly Lachish; David L. Sinn; Nick Beeton; Billie Lazenby (Ecology, 2009)
Most pathogens threatening to cause extinction of a host species are maintained on one or more reservoir hosts, in addition to the species that is threatened by disease. Further, most conventional host–pathogen theory assumes that transmission is related to host density, and therefore a pathogen should become extinct before its sole host. Tasmanian devil facial tumor disease is a recently emerged infectious cancer that has led to massive population declines and grave concerns for the future persistence of this largest surviving marsupial carnivore. Here we report the results of mark–recapture studies at six sites and use these data to estimate epidemiological parameters critical to both accurately assessing the risk of extinction from this disease and effectively managing this disease threat. Three sites were monitored from before or close to the time of disease arrival, and at three others disease was well established when trapping began, in one site for at least 10 years. We found no evidence for sex‐specific differences in disease prevalence and little evidence of consistent seasonal variation in the force of infection. At all sites, the disease was maintained at high levels of prevalence (>50% in 2–3‐year‐old animals), despite causing major population declines. We also provide the first estimates of the basic reproductive rate R 0 for this disease. Using a simple age‐structured deterministic model, we show that our results are not consistent with transmission being proportional to the density of infected hosts but are consistent with frequency‐dependent transmission. This conclusion is further supported by the observation that local disease prevalence in 2–3‐year‐olds still exceeds 50% at a site where population density has been reduced by up to 90% in the past 12 years. These findings lend considerable weight to concerns that this host‐specific pathogen will cause the extinction of the Tasmanian devil. Our study highlights the importance of rapidly implementing monitoring programs to determine how transmission depends on host density and emphasizes the need for ongoing management strategies involving a disease‐free “insurance population,” along with ongoing field monitoring programs to confirm whether local population extinction occurs.

Distribution of microphytobenthic biomass in Martel Inlet, King George Island (Antarctica) - Rodrigo S. P. de Skowronski; Paula F. Gheller; Sandra Bromberg; Carlos J. David; Mônica A. V. Petti; Thaïs N. Corbisier (Polar Biology, 2009)

Plant–pollinator networks: adding the pollinator’s perspective - Jordi Bosch; Ana M. Martín González; Anselm Rodrigo; David Navarro (Ecology Letters, 2009)
Pollination network studies are based on pollinator surveys conducted on focal plants. This plant‐centred approach provides insufficient information on flower visitation habits of rare pollinator species, which are the majority in pollinator communities. As a result, pollination networks contain very high proportions of pollinator species linked to a single plant species (extreme specialists), a pattern that contrasts with the widely accepted view that plant–pollinator interactions are mostly generalized. In this study of a Mediterranean scrubland community in NE Spain we supplement data from an intensive field survey with the analysis of pollen loads carried by pollinators. We observed 4265 contacts corresponding to 19 plant and 122 pollinator species. The addition of pollen data unveiled a very significant number of interactions, resulting in important network structural changes. Connectance increased 1.43‐fold, mean plant connectivity went from 18.5 to 26.4, and mean pollinator connectivity from 2.9 to 4.1. Extreme specialist pollinator species decreased 0.6‐fold, suggesting that ecological specialization is often overestimated in plant–pollinator networks. We expected a greater connectivity increase in rare species, and consequently a decrease in the level of asymmetric specialization. However, new links preferentially attached to already highly connected nodes and, as a result, both nestedness and centralization increased. The addition of pollen data revealed the existence of four clearly defined modules that were not apparent when only field survey data were used. Three of these modules had a strong phenological component. In comparison to other pollination webs, our network had a high proportion of connector links and species. That is, although significant, the four modules were far from isolated.

Exopolysaccharide from surface-liquid culture of Clonostachys rosea originates from autolysis of the biomass - Graciele Viccini; Thalita Romano Martinelli; Regielly Caroline Raimundo Cognialli; Rodrigo Otávio de Faria; Elaine Rosechrer Carbonero; Guilherme Lanzi Sassaki; David Alexander Mitchell (Archives of Microbiology, 2009)

Does seston size structure reflect fish-mediated effects on water quality in a degraded semiarid wetland? - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Miguel Alvarez-Cobelas; Carmen Rojo (Environmental Monitoring and Assessment, 2007)

On the Importance of Water Depth, Macrophytes and Fish in Wetland Picocyanobacteria Regulation - David G. Angeler; Salvador Sánchez-Carrillo; Maria A. Rodrigo; Olga Viedma; Miguel Alvarez-Cobelas (Hydrobiologia, 2005)

Inferring nocturnal surface fluxes from vertical profiles of scalars in an Amazon pasture - Otávio C. Acevedo; Osvaldo L. L. Moraes; Rodrigo Da Silva; David R. Fitzjarrald; Ricardo K. Sakai; Ralf M. Staebler; Matthew J. Czikowsky (Global Change Biology, 2004)
Ecosystem carbon budgets depend on there being good representative surface flux observations for all land use types during the entire diurnal cycle. In calm conditions that often occur at night, especially in areas of small roughness (such as pastures), ecosystem respiration rate is poorly measured using the eddy covariance (EC) technique. Nocturnal vertical profiles of temperature, humidity and winds were observed using tethered balloon soundings in a pasture in the eastern Amazon during two campaigns in 2001. The site is characterized by very weak winds at night, so that there is insufficient turbulence for the EC technique to determine fluxes accurately. To compensate, the time evolution of the profiles is used to determine surface fluxes at early morning and these are compared with those observed by EC at a nearby micrometeorological tower. The nocturnal boundary layer thickness h is determined as the height to which the surface fluxes must converge so that energy budget closure is achieved. The estimated values range from 30 m, around 22:00 hours LST, to more than 100 m just before dawn. These are in good agreement with the observed thickness of a frequently observed fog layer during the middle of the night. During the early portion of the night, when the accumulation layer is shallow, there is appreciable decrease of dCO 2 /d t with height. On calm nights, CO 2 accumulation rate is larger near the surface than at higher levels. On windier nights, this accumulation rate is vertically uniform. Hence, extrapolation of tower profiles for estimating fluxes must be done carefully. Although uncertainties remain large, an alternate approach to the EC method is described for measuring nighttime surface CO 2 fluxes under stable atmospheric conditions.

Land‐use change effects on local energy, water, and carbon balances in an Amazonian agricultural field - Ricardo K. Sakai; David R. Fitzjarrald; Osvaldo L.L. Moraes; Ralf M. Staebler; Otávio C. Acevedo; Matthew J. Czikowsky; Rodrigo da Silva; Eleazar Brait; Valdelirio Miranda (Global Change Biology, 2004)
To study how changing agricultural practices in the eastern Amazon affect carbon, heat and water exchanges, a 20 m tower was installed in a field in August 2000. Measurements include turbulent fluxes (momentum, heat, water vapor, and CO 2 ) using the eddy covariance (EC) approach, soil heat flux, wind, and scalar profiles ( T , q , and CO 2 ), soil moisture content, terrestrial, total solar radiation, and photosynthetically active radiation (PAR, 400–700 nm). At the beginning of the measurements, in September 2000, the field was a pasture. On November 2001, the pasture was burned, plowed, and planted in upland (nonirrigated) rice. Calm nights were the norm in this site. Anomalously low values of net ecosystem exchange (NEE) were found using the EC method, even when the common criterion u * −1 was used to identify and exclude poor performance nights. We observed more plausible values of NEE using criterion u * −1 , indicating that the criterion must be revised downward for flow over surfaces smoother than forests. However, even using the lower threshold, u * was lower than this limit for 82% of nights, and this led to nocturnal respiration underestimates. We compensate for this difficulty by estimating the respiration rate using the nocturnal boundary layer budget method. Land‐use change from pasture to rice cultivation strongly affected both diurnal rates of turbulent exchange but also the pattern of seasonal variation. Seasonal wet and dry season differences in vegetation state were clearly detected in the albedo and PAR‐albedo. These reflectivity changes were accompanied by modified net radiative flux, turbulent heat flux and evaporation rates. The highest evaporation rate was observed during the rice crop, when the field had total evaporation approximately half the precipitation input, less than that of the surrounding forest. Effects of the land‐cover changes were also detected in the carbon budget. For the pasture, the maximum CO 2 uptake occurred in May, appreciably delayed from the start of the rainy season. After the field was plowed and the soil was exposed and there was efflux of CO 2 to the atmosphere day and night for an extended period. Highest values of carbon uptake occurred during the rice plantation. Although the upland rice took up carbon at double the rate of the pasture that it replaced, the field was left fallow for much of the year, during the dry season.

Influence of photoperiod on the overwintering induction of Galerucella calmariensis L - Rodrigo A.M. Velarde; Robert N. Wiedenmann; David J. Voegtlin (BioControl, 2002)

Molecular characterisation of a NADH ubiquinone oxidoreductase subunit 5 from Schistosoma mansoni and inhibition of mitochondrial respiratory chain function by testosterone - Marcelo Rosado Fantappié; Antônio Galina; Ricardo Luís de Mendonça; Daniel Rodrigues Furtado; W. Evan Secor; Daniel G. Colley; Rodrigo Corrêa-Oliveira; George Freeman; Antônio Jorge Tempone; Lia Lannes de Camargo; Franklin David Rumjanek (Molecular and Cellular Biochemistry, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)